Timing of the world-class Yifeng rare metal (Li–Nb–Ta–Rb–Be) mineralization, Jiangnan orogenic belt (South China): Constraints from in situ multi-mineral UPb geochronology - Wei Zheng; Shu-qin Li; Hong-xin Huang; Xian-jun Zhou; Bo Xing; Jing-wen Mao (Journal of Geochemical Exploration, 2026)

Molecular cloning, characterization, and expression analysis of two GABAA receptor-associated proteins (GABARAP and GABARAPL2) from cephalopod Sepiella japonica - Shu-fan Yu; John Praygod Kimaro; Xu Zhou; Shuang Li; Li-bing Zheng; Chang-feng Chi (Molecular Biology Reports, 2026)

ANGPTL4 in gestational diabetes: a diagnostic biomarker linked to placental senescence - Yu-Feng He; Hui Chen; Chuan-Meng Zhang; Su-Su Yang; Xiao-Long Yang; Li-Shuai Jiang; Fan Wang; Shu-Guang Zhou (Functional & Integrative Genomics, 2026)

Synergistic mixed-valence Cu1.8S for superior sulfur-resistant mercury capture from non-ferrous smelting flue gas - Zhou Zhou; Yongqiang Shu; Yue Liu; Su Wang; Xuan Wang; Zhaolian Ye; Haizhou Cao; Zhihe Jin; Zhen Li; Songjian Zhao (Fuel, 2026)

Saccharomycopsis fibuligera solid-state fermentation of wheat bran for glutathione enrichment and functional improvement - Shu Jiang; Lin Zhou; Weiwei Dong; Jinshan Li; Yongmei Hu; Nan Peng; Shumiao Zhao (Food Research International, 2026)

Genomic and food-safety evaluation of Staphylococcus chromogenes in Chinese dairy milk - Xiaoping Li; Baoling Zhang; Tao Zhou; Moli Li; Kai Chen; Shu Li; Xiaofang Tong; Herman W. Barkema; Diego B. Nobrega; John P. Kastelic; Yuqiong Li; A Yao; et al. (Food Research International, 2026)

Rheological scaling for granular systems with varying size, density, and friction: implications for rock-ice avalanches - Chongqiang Zhu; Linghao Peng; Hekai Li; Shu Zhou; Yu Huang; Jin Sun (Computers and Geotechnics, 2026)

Mapping potential conflicts between exotic and native mangroves under human and climate scenarios: A spatial assessment framework in Guangdong, China - Luyao Niu; Jia Sun; Zhi-Wei Hou; Xiankun Yang; Chunxia Zhang; Ji Yang; Wenlong Jing; Tong Jiang; Sijing Shu; Xiaoling Yin; Zikang Li; Chenghu Zhou (Ocean & Coastal Management, 2026)

Three 9-amino-1,10-anthracenedione derivatives with anti-MRSA/VRE activity from Fusarium sp. - fermented Cassia obtusifolia seeds - Zhi-Da Jin; Dai-Hua Fu; Guang-Sen Mou; Yi-Nong Wang; Xiao-Dong Luo; Hao Zhou; Shu-Kun Tang; Li-Xing Zhao (Phytochemistry, 2026)

Integrated analysis of lipid remodeling and volatile evolution during refining of Antarctic krill oil - Xinya Huang; Meiyu Zheng; Jin Zhang; Jinglun Zhou; Qingyang Zhang; Zhengting Zhu; Ping Kong; Shu Wang; Bin Li; Zhigang Hu; Kangyu Zhao; Dongping He; et al. (Food Chemistry, 2026)

Common carp USP30s restrict SVCV replication by attenuating mitophagy - Chen Li; Songjie Qi; Mengxi Zhang; Yunli Zhang; Shu Zhou; Jiangxing Dong; Xianghui Kong (Fish & Shellfish Immunology, 2026)

Janus dual-nitride heterostructure on nanoporous metal for highly selective urea oxidation-assisted hydrogen production - Zhi-Lan Zhou; Jin-Peng Li; Ying Wang; Rui-Qi Yao; Xin-Ying Sun; Shu-Pei Zeng; Yun-Fei Chang; Gao-Feng Han; Tong-Hui Wang; Zi Wen; Hang Shi; Xing-You Lang; et al. (Chemical Engineering Journal, 2026)

A source-reduction process via mechanical activation assisted K2SO4 roasting and closed-loop recycling of potassium salt for efficient lithium extraction from lepidolite - Dong-qi Song; Shu-hao Dong; Long-long Zhou; Zi-ang Si; Shuai-bo Geng; Huan Li; Hui Guo (Chemical Engineering Journal, 2026)

The influence of replacing soybean meal with corn gluten meal on the digestive and absorptive capacity and amino acid metabolism of sub-adult grass carp (Ctenopharyngodon idella) - Yan Liu; Xiao-Qiu Zhou; Lin Feng; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Wen-Jie Tang; Cheng-Bo Zhong; Pei Wu (Aquaculture, 2026)

Iron-bearing halloysite for wetland remediation: Curvature-controlled oxidation pathways and ecological implications - Zihan Shu; Zhiyan Feng; Chencheng Qin; Aoqiang Shu; Limei Shi; Miao Li; Zichen Shangguan; Wenyan Zhou; Ying Li; Xingzhong Yuan; Hou Wang (Water Research, 2026)

Ultrasound-activated endoplasmic reticulum-targeting piezoelectric nanoagonist with auxiliary intrinsic efficacy reverses tumor immunosuppression via spatiotemporal ICD in ovarian cancer - Shuangshuang Cheng; Haojia Li; Yuwei Yao; Ting Zhou; Wan Shu; Jiarui Zhang; Tangansu Zhang; Guanglei Zhong; Guanxiao Chen; Xiaoyu Shen; Yingying Peng; Shuyang Yu; et al. (Chemical Engineering Journal, 2026)

Differentiated provisioning in a mobile royal camp: zooarchaeological and stable isotope evidence from Houmingzi, a locality within a Liao–Jin spring nabo site complex, Northeast China - Wuyu Zhou; Yuanyuan Chen; Shu Wang; Zongyu Li; Yunxin Fu; Enxue Feng; Chunxue Wang; Song Wu (Archaeological and Anthropological Sciences, 2026)

Delta-Band Dynamics of CaMKI-Positive Preoptic Neurons Encode Thermal Homeostatic Information - Dian-Dian Wang; Run-Zhou Yang; Song-Tang Sun; Ya-Lun Sun; Rui-Yu Wang; Xiao-Yan Meng; Sen-Miao Li; Jia-Kang Li; Pei-Pei Liu; Shu-Ang Li; Jian-Sheng Kang (Neuroscience Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Corrigendum to “Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines”, J. Hazard. Mater. (2026) 142537 - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

Atmospheric bulk deposition of microplastics in Jiuzhaigou World Natural Heritage Site: Tourism-associated divergence between particle number and polymer mass fluxes - Ting Liu; Yunqian Chen; Weiyang Xiao; Lv Zhou; Yutao Cao; Philip K. Hopke; Dongmei Liu; Jiangbin Shu; Hui Liu; Rongqiu Li; Xue Qiao (Journal of Hazardous Materials, 2026)

Fluoride-induced male reproductive toxicity: Dual-tissue pyroptosis in the gut-testis axis mediated by inflammatory cytokines - Shu Niu; Yuhui Du; Bin Liu; Zichen Feng; Guoqing Wang; Chunxiang Li; Yan Wang; Qing Sun; Fangfang Yu; Guoyu Zhou; Yue Ba (Journal of Hazardous Materials, 2026)

Mineral carbonation: Processes, mechanisms, and its role in the carbon–hydrogen cycle - Dingkui Zhou; Shuyun Cao; Xiaowen Li; Xuemei Cheng; Jianhua Liu; Yanlong Dong; Lefan Zhan; Shichang Wu; Shu Jiang; Guanzhong Shi (Earth-Science Reviews, 2026)

CHBP-loaded mesoporous polydopamine nanoparticles attenuate neuroinflammation and reprogram microglia-neuron crosstalk for spinal cord injury repair - Linyi Xiang; Jiacheng Zhang; Yuzhe Wu; Jingwei Shi; Yun Shu; Ruize Miu; Jiayi Zhao; Junsheng Zhu; Zhichao Tao; Yibo Geng; Haojie Zhang; Zhenglin Li; et al. (Chemical Engineering Journal, 2026)

Survey on Dioxin Contamination in Chinese-Produced Pesticides and Evaluation of Dioxin Emissions During their Application - Wei Xie; Ya-chen Zhou; Bin Fang; Hui-li Ma; Na Li; Shu-qi Zhang (Water, Air, & Soil Pollution, 2026)

Correction to: Oryzifoliimicrobium ureilyticum gen. nov., sp. nov., a Novel Phosphate‑Solubilizing and Siderophore‑Producing Bacterium Within the Family Rhizobiaceae - Guo‑Hong Liu; Ling Yao; Peng Gao; Shu‑Qun Zhang; Bing Li; Christopher Rensing; Wen‑Qing Li; Shun‑Gui Zhou (Current Microbiology, 2026)

Dendrobium officinale leaf extract extends the mean lifespan in Caenorhabditis elegans via the DAF-16/SOD-3 axis - Cheng Gong; Shu Feng; Yuanfeng Chen; Huiqing Luo; Siyu Zhou; Shikuan Zhao; Rui Zhou; Li Feng; Yunfei Ge; Ruijuan Yang; Chongye Fang; Xiaocui Du (Biogerontology, 2026)

Age outweighs route for AAV-PHP.eB transgene distribution via inner ear delivery - Shuang Han; Yi Zhou; Honghai Tang; Shao Wei Hu; Guannan Geng; Ziting Chen; Sen Zhang; Hongbo Tang; Huawei Li; QingShan Jiang; Yilai Shu (Drug Delivery and Translational Research, 2026)

Impact of boundary layer schemes in RegCM-Chem on East Asian climate and its response to the aerosol-radiation interaction - Heng Cao; Bingliang Zhuang; Yinan Zhou; Peng Gao; Yaxin Hu; Tijian Wang; Shu Li; Mengmeng Li; Min Xie; Qian Liu (Atmospheric Research, 2026)

Bioactive coumarins and chromones with anti-neuroinflammatory effect from Gerbera piloselloides - Cong Zhang; Kuan Lin; Qing-Qin He; Hao Gong; Li-Juan Hu; Mei Zhou; Shi Chen; Wei Liu; Xian-Sheng Ye; Xi-Ji Shu (Phytochemistry Letters, 2026)

Low-dose fluoride and lead co-exposure alters bone mineral density in youth: A nationally representative cross-sectional study - Chunxiang Li; Zeyuan Niu; Yuhui Du; Lihong Yang; Fan Wu; Xinxin Hu; Xiaohang Meng; Zichen Feng; Shu Niu; Qing Sun; Yan Wang; Xiaoli Fu; et al. (Journal of Trace Elements in Medicine and Biology, 2026)

Multi-omics insights into regulatory control of lipid biosynthesis during oil palm fruit maturation - Huangying Shu; Muhammad Imran; Ruoru Zhou; Xiaoyun Peng; Zhen Zhao; Zongming Li; Penghui Liu; Dong Tan; Xianhai Zeng (Food Chemistry, 2026)

Correlation study between sesame seeds roasting conditions and the physicochemical characteristics, hazardous substances levels, and volatile substances profile of hot-water-substitution extracted flavor sesame (Sesamum indicum L.) oil - Li Zhou; Qingyang Zhang; Jin Zhang; Jinglun Zhou; Xinya Huang; Zhengting Zhu; Siya Zhao; Meiyu Zheng; Yong Yang; Shu Wang; Bin Li; Sihong Zhang; et al. (Food Control, 2026)

Plasma-activated nanocellulose for sustainable Pickering emulsions: Enhanced stability and antibacterial performance - Zhuo Li; Rusen Zhou; Bohan Chen; Baolin Yu; Mengying Zhu; Xiaoran Wang; Jiangling Shu; Dehui Xu; Lu Liu; Yadong Zhao; Renwu Zhou; Dingxin Liu (Carbohydrate Polymers, 2026)

Impacts of vegetation management on pollination network structure and robustness in urban parks: A case study from Beijing Wenyu River Park - Yaxuan Li; Meiling Shu; Chenxi Li; Liwen Liu; Yan Zhou; Lan Wu; Yuyu Wang (Urban Ecosystems, 2026)

Hydroxytyrosol preserves myofibrillar protein integrity in grass carp (Ctenopharyngodon idella): Implications for flesh quality enhancement - Yi-Wei Liao; Pei Wu; Wei-Dan Jiang; Hong-Yun Zhang; Yao-Bin Ma; Yang Liu; Shu-Wei Li; Sheng-Yao Kuang; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2026)

Structural dynamics of chloroplast genome in Paphiopedilum (Orchidaceae): in response to natural hybridization - Xue-Ying Wei; Ai-Qun Hu; Jin Zhou; Jiang-Ping Shu; Wei-Yue Sun; Li-Qiang Li; Jian-Wen Shao; Hui Wang; Yue-Hong Yan (Molecular Phylogenetics and Evolution, 2026)

Ship accessibility assessment based on POLARIS and icebreaking capabilities in Arctic area - Hailong Cui; Zhao Liu; Wenyang Xu; Xiyu Zhang; Li Zhou; Wengang Mao; Yaqing Shu (Journal of Transport Geography, 2026)

Rapid identification and prediction of the botanical origins and main components of Chinese yam based on a multimodal data fusion of near-infrared spectra and visualization image information - Xue-Qing Fan; Ming-Hui Wei; Li Yang; Mei Xue; Chun-Juan Pu; Jian-Mei Yin; Xi-Chen Yang; Pei-Dong Chen; Gui-Sheng Zhou; Tian-Shu Wang; Hui Yan (Food Chemistry, 2026)

Feather-based keratin hydrogels enhanced by multiple hydrogen bonding systems: Application in blasting dust suppression - Gang Zhou; Shu Li; Gang Li; Heng Sun; Yizhen Zhang; Xiaoqiang Cao; Bo Wei; Yan Zhang; Shuailong Li (Chemical Engineering Journal, 2026)

Injectable nanocomposite depot with real-time ultrasound control of osteogenic drug release - Yu Shu; Xiang Zhang; Ruonan Jiang; Shunan Wang; Yin Yi; Wenting Du; Siyi Li; Yuanyuan Liu; Huimin Liang; Pengfei Zhou; Panpan Liang; Jinlin Song; et al. (Chemical Engineering Journal, 2026)

HF(aq) thermodynamics in hydrothermal fluids and implications for metal transport - Wei Zhang; Li Zhou; Qihai Shu; Tinggui Yan; Enlin Yang; Jinyu Liu (Chemical Geology, 2026)

Investigation on cross flow characteristics in a 5 × 5 rod bundle with a bowed central rod based on PIV quantification - Shan Zhou; Jianqiang Shan; Li Jiang; Yudong Zha; Junliang Guo; Tenghua Shu; Miao Gui (Annals of Nuclear Energy, 2026)

Efficient removal of triazole fungicides from water using spent coffee grounds-derived hypercrosslinked polymers: A sustainable approach towards environmental cleanup - Kai Shu; Ran Zhu; Haoze Zhou; Qifan Li; Dongze Wang (Journal of Hazardous Materials, 2026)

Physicochemical and flavor profile characterization of sesame oils from different processing methods: Implications for quality control and market regulation - Yong Yang; Timothy J. Tse; Jinglun Zhou; Fengqin Tu; Huiwen Fang; Martin J.T. Reaney; Meiyu Zheng; Fenfen Lei; Li Zhou; Shu Wang (Food Chemistry, 2026)

Effects of dehulling and microwave treatments on physicochemical characteristics, hazardous compounds levels, and volatile substances in mechanically pressed aroma-enhanced sesame (Sesamum indicum L.) oil production - Meiyu Zheng; Jin Zhang; Siya Zhao; Yong Yang; Shu Wang; Bin Li; Zhigang Hu; Sihong Zhang; Dongping He; Fenfen Lei; Li Zhou (Food Control, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

Soil-damped structure interaction analysis considering deep reinforcement learning-driven soil mesh optimization - Xin Li; Chenying Zhou; Wenhui Shu; Chunxiang Li; Liyuan Cao (Soil Dynamics and Earthquake Engineering, 2026)

Quorum sensing-driven biofilm cathode of Shewanella oneidensis for enhanced uranium adsorption: Elucidating the role of exogenous AHLs and validation in actual uranium-contaminated groundwater - Jing Sun; Hong Shu; Xiaoyan Wu; Tingting Liu; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou; Zhongran Dai; Qian Li (Journal of Hazardous Materials, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Genomic insights into the diversity of rice cultivars developed in Heilongjiang Province, China - Yuhan Zhou; Naixin Liu; Jiaqi Yang; Baicui Chen; Chengxin Li; Fanshan Bu; Sanling Wu; Ziqi Zhou; Qingtao Yu; Qingyao Shu (Journal of Zhejiang University-SCIENCE B, 2026)

Intrinsic fault detectability analysis of the BeiDou constellation using minimal detectable bias - Yunqing Tian; Wenxing Zhou; Li Wang; Bao Shu; Yi Li; Qin Zhang (Advances in Space Research, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Ternary composite fibers for oral anthocyanin delivery: The role of molecular synergy in polyvinyl alcohol/gelatin/pullulan matrices - Guoli Ao; Mingyue Zhao; Falin Sun; Yiwen Bao; Sitong Chai; Yuehua Wang; Xu Si; Chi Shu; Sergey S. Makarov; Anton I. Chudetsky; Rodrigo Quintana Loyola; Baoru Yang; et al. (Food Bioscience, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Coumarins mediate the effects of plant diversity on soil microbial community structure and interaction across diverse soils - Shu Li; Ruimin Li; Yuanyuan Yan; Liangliang Liu; Zhe Su; Yi Ren; Xing Zhou; Zucong Cai; Xinqi Huang (Applied Soil Ecology, 2026)

Ultra-low limit heparin detection based on 11-mercaptoundecanoic acid /chitosan functionalized and AuNPs enhanced fiber surface plasma - Jun Wu; Meijuan Jia; Meihui Zhang; Minglu Li; Shu Fang; Jie Dong; Anhua Dong; Ruotong Tian; Jun Zhou; Changyu Shen (Analytica Chimica Acta, 2026)

Cauliflower mushroom ( Sparassis ): a promising functional food with nutritional and medicinal properties - Zhiheng Qiu; Xiaoyan Zhang; Shuhua Ren; Bei Jiang; Jiazhi Zhao; Meijuan Zhu; Di Zhou; Qian Li; Miao Zhang; Tianlai Li; Lili Shu (Critical Reviews in Food Science and Nutrition, 2026)

Molecular and functional characterization of IL-17R signaling pathway-related genes in cuttlefish Sepiella japonica: Identification, expression pattern and protein interaction - Xu Zhou; Jian-Jun Xie; Shu-Fan Yu; Shuang Li; Chang-Feng Chi (Aquaculture, 2026)

Competitive adsorption behavior of Sb(V) and butyl xanthate in mining composite wastewater on iron modified fly ash: Insights into mechanistic distinctions - Yalu Huang; Baolin Hou; Zhi Li; Jinkai Shu; Renjian Deng; Saijun Zhou; Bozhi Ren; Shijie Zhou; Andrew Hursthouse (Process Safety and Environmental Protection, 2026)

Immunosuppressive spirocyclic labdane diterpenoids from Holocheila longipedunculata - Xiu-Ying Bai; Shu-Xi Jing; Ting-Ting Zhou; Yu Zheng; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Nonstationary groundwater level responses to coupled human–natural drivers in the Baiyangdian Watershed - Long Zhou; Longcang Shu; Xiaoran Yin; Tianyu Zhou; Yuxi Li; Bo Liu; Chengpeng Lu; Pengnian Yang (Journal of Hydrology, 2026)

Selaginella Tamariscina extract reduces UVA-induced skin photodamage via regulating apoptosis and autophagy by AKT phosphorylation - Nan Zhao; Xiandong Zhou; Zhiwei Li; Ling Liang; Jinjing Bao; Xueyi Chen; Peng Shu; Jiangming Zhong (Journal of Photochemistry and Photobiology B: Biology, 2026)

EAME: Element-Aware Multi-UAV distributed autonomous exploration for efficient and complete under-canopy measurements - Yuquan Zhou; Li Yan; Yinghao Zhao; Shaungwei Shu; Yaxi Han; Hong Xie (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Untargeted metabolomics elucidates the enhanced protective effects of blackberry juice fermented with Lacticaseibacillus paracasei on hypothalamic-pituitary-adrenal (HPA) axis neuronal dysfunction - Han Wu; Qing-Ru Di; Anthony Pius Bassey; Shu-Dong Xie; Maria G. Corradini; Jian-Zhong Zhou; Xiao-Li Liu (Food Chemistry, 2026)

A unified intracellular pH landscape with SITE-pHorin: a quantum-entanglement-enhanced pH probe - Shu-Ang Li; Xiao-Yan Meng; Su Zhang; Ying-Jie Zhang; Run-Zhou Yang; Dian-Dian Wang; Yang Yang; Pei-Pei Liu; Jian-Sheng Kang (Science China Life Sciences, 2026)

Tumor Necrosis Factor Alpha-Mediated Interaction Between Microglia and Müller Cells Exacerbates Retinal Ganglion Cell Damage in Experimental Glaucoma - Shu-Ying Li; Hong Zhou; Guoli Zhao; Wen-Wen Ding; Yu Zhang; Yong-Chen Wang; Fang Li; Yanying Miao; Xing-Huai Sun; Zhongfeng Wang (Neuroscience Bulletin, 2026)

Retraction Note to: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2026)

Comparison of soil enzyme activity and stoichiometry between urban park and forest in the Pearl River Delta region, China - Han Sheng; Xu Li; Luis Carlos Ramos Aguila; Fasih Ullah Haider; Shu-Yi-Dan Zhou; Guopeng Wu; Chushu Meng; Yunxuan Deng; Juxiu Liu (Applied Soil Ecology, 2026)

Effects of the dietary proportions of lipids and carbohydrates on milk fat, blood metabolites, and the fecal microbial community in lactating jennies - Shu-xian Zhang; Tao Xu; Qiong-xian Yan; Liang Deng; Allan Degen; Li-lin Liu; Lei Fang; Xiao-ling Zhou (Animal Feed Science and Technology, 2026)

10-Hydroxy-2-decenoic acid ameliorates LPS-induced acute lung injury through targeting MD2-mediated inflammatory signaling pathways - Cong Shu; Chen Li; Huamin Liu; Zengxian Zhou; Chenghao Qian; Zhuohui Xie; Fenfen Lin; Yuxiao Jiang; Ruping Chen; Yue Liu; Xin Liu; Gaozhi Chen; et al. (Toxicology and Applied Pharmacology, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Soil organic carbon decline under bamboo invasion: The role of microbial carbon cycling - Chushu Meng; Chaotang Lei; Xu Li; Han Sheng; Guopeng Wu; Juxiu Liu; Shu-Yi-Dan Zhou (Journal of Environmental Management, 2025)

Morphology-tunable synthesis of two-dimensional silicoaluminophosphate molecular sieves guided by silanol-rich short-range ordered Si species - Shu Liu; Jie Shi; Linyu Zhou; Chan Wang; Qingyan Cui; Tiesen Li; Yuanyuan Yue (Chemical Engineering Journal, 2025)

A flexible Janus triboelectric-piezoelectric hybrid nanogenerator for efficient dust personal protection in high humidity working condition - Gang Zhou; Yunlong Ma; Yueying Xin; Zhuo Xu; Jintuo Zhu; Shu Li; Shengying Zhang; Jialu Pang; Xiaoqiang Cao; Yongmei Wang (Chemical Engineering Journal, 2025)

Association of Serum Neurofilament Light and Glial Fibrillary Acidic Protein with Cerebral Small Vessel Disease in Nondemented Middle-to-Old Aged Population - Xiao-Hong Huang; Feng Gao; Jing Yuan; Ding-Ding Zhang; Mei-Jun Shu; Fei-Fei Zhai; Fei Han; Ming-Yu Tang; Ming-Li Li; Li-Xin Zhou; Jun Ni; Ming Yao; et al. (Translational Stroke Research, 2025)

Holocene moisture and aeolian activity recorded in loess from the Yarlung Tsangpo, Southern Tibetan Plateau - Wenli Li; Weijan Zhou; Peng Cheng; Yuda Chui; Ling Yang; Yan Hu; Jie Zhou; Peixian Shu; Xuefeng Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Composite dust suppression material of fish scale based chitosan intercalated MMT: Synthesis process, performance parameters, and mechanism of action - Gang Zhou; Shu Li; Shuo Lu; Xi Chen; Jingxu Chen; Gang Li; Mengrou Zhao; Hongrui Qu; Shuailong Li (Environmental Research, 2025)

Elevated public health risks from changes in microbial communities mediated by moso bamboo invasion - Ruijia Chen; Xu Li; Chushu Meng; Chaotang Lei; Fasih Ullah Haider; Xu-Jun Liu; Juxiu Liu; Shu-Yi-Dan Zhou (Environmental Research, 2025)

A multi-dimensional approach to assessing source-oriented health risks from heavy metals in coal mining regions - Mengjing Ni; Farui Jiang; Kunyu Li; Qi Liu; Xun Shu; Ting Li; Zijun Zhou; Shirong Zhang; Yulin Pu; Yongxia Jia; Xiaojing Liu (Environmental Pollution, 2025)

Numerical simulation and experimental investigation of an annular tank filled with Zr0.8Nb0.2Co0.6Cu0.15Ni0.25 hydrogen isotope storage alloy - Liyang Shu; Jiacheng Qi; Liujun Zhan; Zhipeng Li; Yang Liu; Jiapeng Bi; Yongpeng Chen; Panpan Zhou; Zhiyi Yang; Xingwen Feng; Huaqin Kou; Changan Chen; et al. (Chemical Engineering Journal, 2025)

Sequential release of an injectable depot simulating the bone healing mechanism based on LIPUS for bone defects repair - Xujia Shan; Xiaoyan Yuan; Siyi Li; Wenting Du; Xiang Zhang; Yin Yi; Yu Shu; Shunan Wang; Ruonan Jiang; Pengfei Zhou; Huimin Liang; Yuanyuan Liu; et al. (Chemical Engineering Journal, 2025)

A novel method to quantify Dendrobium officinale polysaccharides in biological samples via 99mTc-labelling and radioHPGPC analysis - Pengfei Dou; Jinglin Wang; Yamin Shu; Fang Cheng; Gang Nie; Li Luo; Zhijing Wu; Ziming Zheng; Yongkang Gai; Junxi Liu; Yan Liu; Yinxing Zhou; et al. (Carbohydrate Polymers, 2025)

Involvement of ductal reaction in Di-(2-ethylhexyl)-phthalate-caused hepatic fibrosis: Molecular mechanisms and potential intervention strategies - Xinru Du; Shu Zhang; Sha Liu; Yancheng Gao; Zhendong Wang; Na Dong; Sisi Song; Qinming Hui; Ziyi Wang; Yue Ma; Chunxiao Zhou; Ye Yang; et al. (Chemico-Biological Interactions, 2025)

Comparative study of parameterization schemes for aerosol indirect effects in East Asia based on RegCM4 - Runqi Zhao; Yaxin Hu; Bingliang Zhuang; Yinan Zhou; Peng Gao; Heng Cao; Shanrong Liang; Tijian Wang; Shu Li; Min Xie; Mengmeng Li (Atmospheric Environment, 2025)

Tianshan topographic heating and a Central Asian dipole precipitation anomaly in the mid-Holocene - Yingying Sha; Zhengguo Shi; Xiaofei Zhang; Ke Shang; Peng Zhou; Peixian Shu; Jing Lei; Xinzhou Li; Hai Cheng; Zhisheng An (Science China Earth Sciences, 2025)

The cryoprotective effect of virgin coconut oil on boar sperm: Enhancing sperm quality and reproductive performance - Shu Ma; QianXi Liang; Zhili Li; Feng He; Ye Wang; Zhanwei Zhuang; Jian Zhou; Yunxiang Zhao; Fumei Chen (Animal Reproduction Science, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Intrinsic electron transfer kinetics of electroactive granular sludge bioanode boosting bio-electro-Fenton efficiency - Bao-Gang Fu; Shu-Na Li; Xiangtong Zhou; Xiang Xiao; Liang Cheng; Yang-Yang Yu (Journal of Environmental Chemical Engineering, 2025)

Revealing the mechanisms of riboflavin and choline enhances performance of the anaerobic digestion of food waste: Efficiency, microbial communities, and functional genes - Chengyuan Su; Guangrong Zhou; Fengxiu Ding; Lipeng Wu; Shu Gao; Qiuhong Li; Yuxiang Lu; Peng Zheng; Shenglong Chen (Journal of Environmental Chemical Engineering, 2025)

Production of humic acid mineral fertilizer from coal gangue via urea-assisted low-temperature oxidative cracking: Reaction parameter optimization and mechanism study - Xiaozhen Liu; Zhiguang Yang; Huixin Zhou; Lingwen Dai; Yichao Wang; Xumin Li; Xinqian Shu (Journal of Environmental Chemical Engineering, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Frying characteristics of beef tallow as a potential alternative for intermittent deep-fat frying - Fenfen Lei; Meiyu Zheng; Tianyu Zhang; Timothy J. Tse; Martin J.T. Reaney; Shu Wang; Xiaoming Jiang; Bin Li; Zhigang Hu; Dongping He; Sihong Zhang; Qinfeng Zhang; et al. (Food Chemistry, 2025)

Dietary biotin facilitates collagen deposition and myofiber growth and development, improving muscle chewiness and hardness in grass carp (Ctenopharyngodon idella) - Yang Yang; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng; Xiao-Qiu Zhou (Food Bioscience, 2025)

Comparison of the host-pathogen interactions between Pseudomonas plecoglossicida and Nocardia seriolea in a cell line derived from head kidney of yellow large croaker - Li-Yun Jin; Shu-Ya Li; Fei Yin; Zhen Tao; Xiao Xie; Su-Ming Zhou (Fish & Shellfish Immunology, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

High-throughput real-time detection of sepsis inflammatory biomarker proteins in clinical samples using metasurface plasmon resonance biosensors - Jing Wu; Youqian Chen; Liping Huang; Yuhan Sun; Jingjing Zhao; Xiaoyang Cheng; Ruiwen Sun; Hanlin Zhou; Yue Shu; Wen Li; Wenhong Zhang; Wei Liu; et al. (Chemical Engineering Journal, 2025)

Catalyzing polysulfides redox reactions by p-d orbital hybridized ZnCoSe with built-in electric field - Zhengwei Yang; Peng Zhou; Tianyu Zhang; Jiali Liu; Ningxi Lu; Dengke Li; Min Liu; Guang Li; Jincang Su; Manfang Chen; Xiukang Yang; Hongbo Shu; et al. (Chemical Engineering Journal, 2025)

The Integration of Olink Proteomics with Transcriptomics Elucidates that TNF-α Induces Senescence and Apoptosis in Transplanted Mesenchymal Stem Cells - Yuchuan Zhou; Jianbo Xiao; Shu Peng; Xiao Pang; Daiyuan Ma; Yan Gui; Hongpan Zhang; Zhike Li (Stem Cell Reviews and Reports, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Arsenite antiporters ACR3/3;1 are critical for Se-enhanced plant growth and As accumulation in As-hyperaccumulators Pteris multifida and Pteris cretica - Wei Li; Si-Xue He; Yi-Wen Liu; Qian-Yu Zhou; Shu-Fen Xiao; Yanshan Chen; Yue Cao; Lena Q. Ma (Journal of Hazardous Materials, 2025)

Nanocatalytic-phytoremediation synergistic strategy: Functional carbon nanodots enhancing nonylphenol biodegradation in contaminated soil - Qiong Chen; Junjie Huang; Junbo Zhou; Lanxuan Sun; Jianing Yang; Qiuyu Shu; Yiwen Sun; Juan Li; Mei Yan (Journal of Hazardous Materials, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Incorporating frequency domain features into radiomics for improved prognosis of esophageal cancer - Shu Chen; Shumin Zhou; Liyang Wu; Shuchao Chen; Shanshan Liu; Haojiang Li; Guangying Ruan; Lizhi Liu; Hongbo Chen (Medical & Biological Engineering & Computing, 2025)

Oryzifoliimicrobium ureilyticus gen. nov., sp. nov., a Novel Phosphate-Solubilizing and Siderophore-Producing Bacterium Within the Family Rhizobiaceae - Guo-Hong Liu; Ling Yao; Peng Gao; Shu-Qun Zhang; Bing Li; Christopher Rensing; Wen-Qing Li; Shun-Gui Zhou (Current Microbiology, 2025)

Potential of bio-hydrometallurgical recovery of rare earth elements from secondary resources: Research progress and prospects - Min Huang; Hao Zhou; Shiyu Shao; Xinyi Yu; Xiaojie Shu; Zhu Chen; Guanzhou Qiu; Li Shen; Hongbo Zhao (Journal of Cleaner Production, 2025)

Nanocellulose improves viscoelasticity and freeze-thaw stability of water-in-oil emulsion gels - Xin Hong; Mingjun Shu; Yuling Zhou; Jieying Li; Jinwei Li (Food Chemistry, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Effect of molecular weight of water-based sizing agents on CF processability and CF/PPS composite performance - Shu Zhu; Mengtong Li; Yang Yang; Tianwen Yan; Xuran Ruan; Yu Zhang; Liusheng Zha; Jianfeng Zhou; Yu Gao (Chemical Engineering Journal, 2025)

Interfacial strength vs toughness: Enhancing mechanical and impact performance of CF/PEEK thermoplastic composites - Yu Gao; Song Yan; Kaiyan Min; Xiahui Liu; Yue Li; Ju Wu; Jianfeng Zhou; Shu Zhu; Peng Wang (Chemical Engineering Journal, 2025)

MiR-21-5p promotes RPE cell necroptosis by targeting Peli1 in a rat model of AMD - Yishun Shu; Ziwen Li; Tianyi Zong; Tong Mu; Haoyuan Zhou; Qian Yang; Meili Wu; Yanqiu Liu; Tianhua Xie; Chengye Tan; Miao Zhuang; Xiaolu Wang; et al. (In Vitro Cellular & Developmental Biology - Animal, 2025)

Biodegradable Mg–Cu alloy inhibits HBV replication and hepatocellular carcinoma progression - Heyu Zheng; Weiping Zhou; Meiqi Mao; Yiwei Wang; Xing Tian; Biao Yang; Lu Zhao; Shu Li; Ye Sun; Zhongjia Jiang; Ronghua Fan; Yuxin Bai; et al. (BioMetals, 2025)

Bacillus velezensis YN2111 reveals the potential role of amine oxidase in Fusarium wilt response in Cavendish bananas - Hongwei Yu; Guangdong Zhou; Wenlong Zhang; Bonaventure Aman Omondi; Alberto Cenci; Kunhua Liu; Juhua Liu; Huacai Fan; Shu Li; Mathieu Rouard; Si-Jun Zheng (Physiological and Molecular Plant Pathology, 2025)

Health risk assessment of source-specific elemental carbon (using dual carbon isotopes) and heavy metals in the Tibetan Plateau - Ju-Lian Shi; Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Lu-Yao Wang; Qian Li; Qi-Yuan Wang; Sui-Xin Liu; Jun-Ji Cao (Journal of Hazardous Materials, 2025)

Drivers for the trends of atmospheric inorganic nitrogen deposition in China under the past and future scenarios - Zihan Zhang; Dan Yan; Mengmeng Li; Yuting Lu; Yiting Zhou; Tijian Wang; Bingliang Zhuang; Shu Li; Xin Huang (Atmospheric Environment, 2025)

Traditional Chinese Medicine, Ziyin-Mingmu Decoction, Regulates Cholesterol Metabolism, Oxidative Stress, Inflammation and Gut Microbiota in Age-related Macular Degeneration Models - Xing Li; Khalid S. Ibrahim; Michal R. Baran; Gabriel Mbuta Tchivelekete; Xinzhi Zhou; Yi Wu; James Reilly; Zhoujin Tan; Zhiming He; Xinhua Shu (Pharmaceutical Research, 2025)
Background Age-related macular degeneration (AMD) is the commonest cause of retinal disorders in the aged population. Ziyin-Mingmu decoction (ZD) has been widely used to treat AMD patients over thousands of years, however the underlying functional mechanisms of ZD are largely elusive. In this study, we aim to elucidate the therapeutic mechanisms of ZD in AMD models. Methods An in vivo AMD mouse model and an in vitro AMD model were established. Cholesterol level in mouse tissues was measured. Expression of antioxidant genes and proinflammatory cytokines in mouse tissues and in human retinal pigment epithelial (RPE) cells were detected using biochemical approaches. Gut microbiota community and functional pathways were analysed using bioinformatics approach. Compounds in ZD were identified using HPLC/MS. Results High fat diet (HFD)-fed mice had significantly higher levels of cholesterol in the retina, RPE, liver and serum, and markedly decreased expression of cholesterol metabolism-associated genes in those tissues, compared to mice fed with normal diet. Similarly, expression of antioxidant and inflammation genes was dysregulated in HFD-fed mouse tissues. ZD treatment reversed these HFD-induced pathological effects. HFD also altered the composition of cecum bacterial communities and associated metabolic pathways, which returned to control levels by ZD. In vitro assays showed that H 2 O 2 significantly increased oxidative stress and enhanced expression of proinflammatory cytokines. Co-treatment with ZD significantly counteracted these changes. HPLC/MS identified 105 compound in water extracted ZD and most are polyphenols. Conclusion Our data suggests that protection of ZD against AMD is possibly through mitigating cholesterol level, oxidative stress and inflammation, and modulating gut microbiota by polyphenols.

A Deep Learning Framework for Parameter Estimation in 1D Marine Ecosystem Model - Ao Li; Kewei Zhao; Weiwei Fang; Chan Shu; Runjie Zhou; Qiuyi Li; Xiaolong Huang; Xiaohong Lei; Menghan Xu; Haoyu Jiang; Lin Mu (Journal of Marine Science and Engineering, 2025)
Marine ecosystems play an increasingly critical role in both global climate regulation and the impacts of anthropogenic activities. Accurate marine biogeochemical numerical models are essential tools for understanding and predicting the complex dynamics of these systems. However, as model complexity increases, so does the number of biological parameters and the uncertainties associated with them, which can substantially affect model performance. Consequently, efficient and reliable parameter estimation has become a key challenge in model development and application. In this study, we proposed a deep learning-based approach for parameter estimation in numerical models, utilizing deep neural networks to capture the complex nonlinear relationships between numerical model input parameters and output variables. A one-dimensional marine ecosystem model is employed as a case study to evaluate the effectiveness of the proposed method. The results demonstrate that (1) the deep learning approach provides an automated and adaptive solution for parameter estimation, significantly improving the efficiency of model calibration in engineering and scientific applications by enabling rapid identification of near-optimal parameter sets; and (2) the deep learning model effectively learns the underlying nonlinear mappings between inputs and outputs. During training, the mean squared error (MSE) loss exhibits a steady decline, with minor fluctuations in the early stages, ultimately converging to a stable value. The predicted parameter combinations show strong agreement with the reference numerical model outputs, yielding correlation coefficients exceeding 0.95.

Gut microbiota modulation: a narrative review on a novel strategy for prevention and alleviation of ovarian aging - Wei Lyu; De-Feng Li; Shu-Ying Li; Hua Hu; Jian-Yun Zhou; Ling Wang (Critical Reviews in Food Science and Nutrition, 2025)

A nutritional strategy for improving sub-adult grass carp (Ctenopharyngodon idella) flesh flavor: The role of α-lipoic acid in regulating muscle nucleotide and fatty acid metabolism - Yang Zhang; Pei Wu; Wei-Dan Jiang; Yang Liu; Yao-Bin Ma; Sheng-Yao Kuang; Shu-Wei Li; Ling Tang; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Corrigendum to “Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella)” [Aquaculture Volume 598, 15 March 2025, 742053] - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Dynamic environment but no temperature change since the late Paleogene at Lühe Basin (Yunnan, China) - Caitlyn R. Witkowski; Vittoria Lauretano; Alex Farnsworth; Shu-Feng Li; Shi-Hu Li; Jan Peter Mayser; B. David A. Naafs; Jingyi Wei; Robert A. Spicer; Tao Su; He Tang; Zhe-Kun Zhou; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Chemical property, bioactive constituent and volatile compound changes of beef tallow during an improved flavor-retaining refining approach - Li Zhou; Meiyu Zheng; Tianyu Zhang; Shu Wang; Xiaoming Jiang; Bin Li; Zhigang Hu; Timothy J. Tse; Martin J.T. Reaney; Qiangsheng Nie; Dongping He; Chuanrong Hu; et al. (Food Chemistry, 2025)

Physicochemical analysis of beef tallow and its liquid fraction, comparing frying performance with high oleic acid rapeseed oil and rice bran oil - Fenfen Lei; Meiyu Zheng; Tianyu Zhang; Shu Wang; Bin Li; Dongping He; Sihong Zhang; Li Zhou; Qinfeng Zhang; Zhigang Hu (Food Chemistry, 2025)

Integration of Morris and GLUE methods for improving massflow-based debris flow simulation - Haibo Yang; Jiaqi Huang; Xinyi Liu; Peng Xu; Bo Yu; Jinjun Guo; Junhua Li; Yuhang Zhou; Xiaosong Shu (Natural Hazards, 2025)

Seasonal Variation of Phyllosphere Microbial Communities Under Warming - Chaotang Lei; Shu‐Yi‐Dan Zhou; David T. Tissue; Roy Neilson; Zhiyang Lie; Ting Wu; Xujun Liu; Chushu Meng; Xu Li; Dong Zhu; Juxiu Liu (Global Change Biology, 2025)
The phyllosphere is a complex microbial ecosystem residing on plant leaves, hosting microbes that influence plant growth and fitness. The phyllosphere is sensitive to temperature and moisture, so understanding its response to climate warming and variable moisture associated with changes in seasons is crucial for predicting ecosystem function. We conducted a 12‐year warming experiment in a sub‐tropical forest by transplanting a natural ecosystem from higher to lower elevations. We sampled phyllosphere microbial communities across wet and dry seasons for three consecutive years (years 10–12) to assess potential adaptation strategies to warming. Phyllosphere microbial community structure and diversity varied seasonally, with higher bacterial richness in the dry season; however, warming reduced bacterial richness across seasons. Co‐occurrence networks revealed stronger microbial interactions in the dry season, which exhibited reduced connectivity under warming. Community assembly was largely stochastic, with warming enhancing species turnover and dispersal. Notably, plant probiotics, enriched in the wetter season with greater environmental disturbances, played a key role in adaptation to seasonal changes and warming. Seasonal shifts in microbial function were observed: wet‐season bacteria were enriched in carbohydrate and energy metabolism, while dry‐season bacteria showed elevated sulfur metabolism, reflecting adaptive metabolic strategies to environmental conditions. Our study enhances the understanding of the seasonal patterns of phyllosphere microbial communities and the impact of climate warming, offering new insights into plant–microbial adaptation strategies in response to climate change.

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Electroactive biofilms alter the EPS structure and metabolic pathways to sense potential and tetracycline - Fenglin Li; Lean Zhou; Shu Wang; Yongliang Wu; Tian Li; Shiquan Sun; Jinting Wang (Journal of Hazardous Materials, 2025)

Dust emissions in the arid Asian interior and abrupt changes in midlatitude atmospheric circulation during the glacial-Holocene transition - Peixian Shu; Dongfeng Niu; Yougui Song; Yuejun Si; Shugang Kang; Baosheng Li; Weijian Zhou; Zhisheng An (Global and Planetary Change, 2025)

Electric field-driven preparation of highly dispersed ENP membrane and its study on Cr(VI) removal from water - Yangshuo Sun; Guiyang Jiang; Yiming Zhou; Leilin Shu; Jiarui Li; Longcheng Liu; Junzhe Zhang; Xunrui Cheng; Yiyun Liu; Xiaoyan Xu; Zhi Zhu; Junshan Liu; et al. (Chemical Engineering Journal, 2025)

Large-scale synoptic and weather drivers for the co-occurrence of fine particulate matter and ozone extremes over China - Wei Wang; Yiting Zhou; Mengmeng Li; Yuting Lu; Xinyi Jiang; Tijian Wang; Bingliang Zhuang; Shu Li; Chenchao Zhan; Xiaoyun Sun; Xin Huang (Science China Earth Sciences, 2025)

Analysis of the effect of 60 Co irradiation sterilization on the chemical composition of volatile organic compounds in Rhizoma Acori Tatarinowii using GC-IMS - Man-Shu Zou; Li-Yan Xie; Wei Zhou; Yun Xiang; Chang Lei; Dan Huang (Natural Product Research, 2025)

An approximate analytical solution on the scattering of sound by a Taylor Vortex - Xun Yuan; Yiqing Shu; Fuchun Zhang; Penglai Guo; Weicheng Chen; Kai Fang; Yingfang Zhang; Xiaoji Zhou; Jianqing Li (Wave Motion, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Soil and litter microbiomes as joint drivers of ecosystem multifunctionality in a 60-year-old forest plantation - Shu-Yi-Dan Zhou; Xu Li; Josep Peñuelas; David T. Tissue; Roy Neilson; Xujun Liu; Zhiyang Lie; Fu-Yi Huang; Junhua Yan; Dong Zhu; Juxiu Liu (Journal of Environmental Management, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Novel nutritional strategy: Dietary valine improves the health value and nutrient deposition in grass carp (Ctenopharyngodon idella) - Meng-Ling Cai; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Shu-Wei Li; Ling Tang; Cheng-Bo Zhong; Lin Feng (Aquaculture, 2025)

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Influence of ship emitted sulfur and carbonaceous aerosols on East Asian climate in summer - Bingliang Zhuang; Yinan Zhou; Yaxin Hu; Shanrong Liang; Peng Gao; Yiman Gao; Huimin Chen; Shu Li; Tijian Wang; Min Xie; Mengmeng Li (Atmospheric Environment, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

cascAGS: Comparative Analysis of SNP Calling Methods for Human Genome Data in the Absence of Gold Standard - Qianqian Song; Taobo Hu; Baosheng Liang; Shihai Li; Yang Li; Jinbo Wu; Shu Wang; Xiaohua Zhou (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Expression of a Colletotrichum polyketide synthase gene in Aspergillus nidulans leads to unexpected conjugates with a host metabolite - David Breyer; Leyao Chen; Jenny Zhou; Zhang-Hai Li; Shu-Ming Li (Archives of Microbiology, 2025)
Heterologous expression of the putative 1,3,6,8-tetrahydroxynaphthalene synthase gene ChPKS from Colletotrichum higginsianum in Aspergillus nidulans led to the formation of at least eight new compounds. LC-MS analysis proved them as coupling products of 1,3,6,8-tetrahydroxynaphthalene with an intermediate of the cichorine biosynthetic pathway. Comprehensive NMR analysis confirmed the structures of the two predominant products higginidulans A and B. Deletion of the backbone gene of the cichorine pathway in host strain Aspergillus nidulans abolished the formation of higginidulans. Heterologous expression of ChPKS in the alternative Penicillium crustosum expression host resulted in the formation of the expected product 1,3,6,8-tetrahydroxynaphthalene, which was confirmed by acetylation and structural elucidation. This study provides an additional example of unexpected natural product formation by crosstalk of biosynthetic pathways derived from different species. Moreover, it highlights the importance of using alternative host systems for gene expression.

Suyin Detoxification Prescription Regulates the Klotho and ERK/NF-κB Signaling Pathways to Alleviate Renal Injury - Lianghui Shu; Li Quan; Yanping Wang; Yanlin Chen; Chen Yong; Fang Tian; Kun Gao; Enchao Zhou (Cell Biochemistry and Biophysics, 2025)

Global impacts of land use on terrestrial carbon emissions since 1850 - Xiaodong Yuan; Xiaoyong Bai; Zhongfa Zhou; Guangjie Luo; Junhan Li; Chen Ran; Siri Zhang; Lian Xiong; Jingjing Liao; Chaochao Du; Lei Dai; Zilin Li; et al. (Science of The Total Environment, 2025)

Growth Performance of and Liver Function in Heat-Stressed Magang Geese Fed the Antioxidant Zinc Ascorbate and Its Potential Mechanism of Action - Yanli Ren; Yunan Sun; Hafiz Umer Javad; Renkai Wang; Zhiqing Zhou; Yunmao Huang; Xugang Shu; Cuijin Li (Biological Trace Element Research, 2025)

Potential role of ARG1 c.57G > A variant in Argininemia - Yixiao Li; Rujin Tian; Dong Wang; Haozheng Zhang; Yi Zhou; Chunli Ma; Han Zhang; Kaihui Zhang; Shu Liu (Genes & Genomics, 2025)

Involvement of PRQFVamide-related peptide in immune response of Sepiella japonica through suppressing nitric oxide production - Xu Zhou; Shu-fan Yu; Jia-yin Qiu; Jian-jun Xie; Shuang Li; Li-bing Zheng; Chang-feng Chi (Aquaculture International, 2025)

TDCPP promotes apoptosis and inhibits the calcium signaling pathway in human neural stem cells - Ming-Rui Li; Guo-Rui Zhou; Zi-Ye Wang; Bo-Yang Li; Shu-Hui Men; Zhen-Guang Yan (Science of The Total Environment, 2025)

Seven undescribed compounds from dried flower buds of Ochrocarpus longifolius - Shu-Lan Liu; Xue-Ling Huang; Shun-Hua Zhong; Yong-Hui Ma; Feng Wei; Yu-Ye Zhang; Jin Li; Ke-Jian Pang; Ping Zhao; Xin-Zhou Yang (Phytochemistry, 2025)

Metagenomics and metaproteomics reveal the effects of sludge types and inoculation modes on N,N-dimethylformamide degradation pathways and the microbial community involved - Yunchuan Xian; Linlin Cao; Yuxiang Lu; Qiuhong Li; Chengyuan Su; Yuan He; Guangrong Zhou; Shenglong Chen; Shu Gao (Journal of Hazardous Materials, 2025)

Alteration of nitrogen sink and emission by vegetation distribution in a wetland with significant change in water level - Huazu Liu; Qiu Jin; Xiaoguang Xu; Wei Yang; Megumu Fujiabayashi; Junxiao Luo; Zhexin Li; Chuanqiao Zhou; Pingyin Shu; Wei Li (Journal of Environmental Management, 2025)

Abiotic aerobic oxidation pathways of stibnite revealed by oxygen and sulfur isotope systematics of sulfate - Ningjie He; Shu Li; Xiaoqian Li; Yaning Tang; Jiaxue Yang; Jianwei Zhou (Journal of Environmental Sciences, 2025)

Prediction of hydrate formation boundaries in pure water and salt/alcohol containing systems based on prior knowledge and artificial intelligence - Shu-Kai Chen; Xiao-Fang Lv; Jian-Ping Ding; Yang Liu; Ji-Miao Duan; Hui Du; Chuan-Shuo Wang; Ming-Guo Peng; Qian-Li Ma; Shi-dong Zhou (Fuel, 2025)

Prospective LCA towards achieving carbon neutrality goals: Framework application and challenges - Ya-Xi Fang; Pei-Ze Wu; Sha Chen; Yu Li; Shu-Fen Cui; Jin-Xing Zhu; Hai-Zhou Cao; Ke-Jun Jiang; Ling Zhong (Environmental Impact Assessment Review, 2025)

Dual-mode detection of human immunoglobulin via copper oxide nanozyme catalysis fluorescent species generation and photoelectrochemical alteration in ZnIn2S4/SnO2-based system - Jiawei Zhou; Lili Zhao; Yuee Zhong; Peipei Li; Xiaohua Zhu; Shu Huang; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Dynamic trends in maize diseases and pests across six regions in China over two decades - Hong-ying Cui; Amber Sciligo; Xiao-ling Tan; Cang Hui; Yong-sheng Zhang; Wei Li; Zi-qiao Zhou; Zhen-qing Peng; Ping Ma; Zhi-shu Xiao; Fang Ouyang (Crop Protection, 2024)

Machine learning constructs the microstructure and mechanical properties that accelerate the development of CFRP pyrolysis for carbon-fiber recycling - Lingwen Dai; Xiaomin Hu; Congcong Zhao; Huixin Zhou; Zhiji Zhang; Yichao Wang; Shuai Ma; Xiaozhen Liu; Xumin Li; Xinqian Shu (Waste Management, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Physicochemical properties and flavor substances analyses of refined beef tallow with dry fractionation treatment - Li Zhou; Tianyu Zhang; Meiyu Zheng; Shu Wang; Bin Li; Zhigang Hu; Qiangsheng Nie; Dongping He; Chuanrong Hu; Jingcheng Zheng; Fenfen Lei; Qinfeng Zhang (Food Chemistry, 2024)

Histidine is effective in promoting muscle growth and protein deposition: In vivo and in vitro experimental models of grass carp (Ctenopharyngodon idella) - Xin Zeng; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Ling Tang; Shu-Wei Li; Sheng-Yao Kuang; Lin Feng (Food Bioscience, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Identification of the synonymous variant c.3141G > A in TNRC6B gene that altered RNA splicing by minigene assay - Feiyu Zhou; Hongping Zhong; Bo Wu; Yaqiong Cui; Jiaci Li; Xiaodong Jia; Changshun Yu; Dong Li; Jianbo Shu; Chunquan Cai (Molecular Biology Reports, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Exogenous paths regulate electron transfer enhancing sediment phosphorus immobilization - Lean Zhou; Yuting Zeng; Chong Xu; Naif Abdullah Al-Dhabi; Shu Wang; Shiquan Sun; Jinting Wang; Wangwang Tang; Tian Li; Xin Wang (Science of The Total Environment, 2024)

Characteristics of surface microlayer film under different freshwater environments: Physical, chemical, and biological properties - Yuankun Yang; Tian Ma; Shu Chen; Han Song; Lunzhen Li; Yu He; Tao Song; Qiuhong Zhou; Weiguo Tu (Process Safety and Environmental Protection, 2024)

Baseline sensitivity and resistance risk of Sclerotinia sclerotiorum to glabridin and the possible anti-fungal mechanism - Shu Xu; Chenyang Liu; Jin Chen; Linwei Li; Siwei Qiao; Mei Tian; Qian Zhou; Xingzeng Zhao; Yu Chen; Fei Liu; Xu Feng (Pesticide Biochemistry and Physiology, 2024)

Acne-related UVA-induced facial fluorescence: An exploratory study from physiological properties to tissue structure information - Xing Ren; Yanan Sun; Yuxin Zhang; Na Zhou; Yunong Wang; Lishuang Li; Xinyu Gao; Yuman Ma; Xianyu Li; Zhe Shu; Honghui He; Yi Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Hybrid 2D/3D carbon framework confined Si with optimized reaction kinetics for highly stable Li-Ion storage - LiLin Lin; Peijun Zhou; Wen Xiong; Tingting Zhao; Shengsong Li; Liangui Yang; Tao Meng; Junhao Zhong; Zhibiao Cui; Dong Shu (Chemical Engineering Journal, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Exploring the Potential of MIM-Manufactured Porous NiTi as a Vascular Drug Delivery Material - Yang Zhou; Tun Wang; Peng Lu; Zicheng Wan; Hao He; Junwei Wang; Dongyang Li; Yimin Li; Chang Shu (Annals of Biomedical Engineering, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

New role of radical-induced polymerization: Base/self-heating synergistically activate persulfate to boost food waste humification - Dongqing Cai; Xiaoya Pan; Chengjin Wang; Shihu Shu; Pengjin Zhu; Chunhuo Zhou; Dongfang Wang; He Xu; Yanbiao Liu; Wenhai Chu; Xiang Li; Yanping Zhu (Journal of Cleaner Production, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Preparation of high V-type relative crystallinity dextrin from V-type granular starch via high-temperature acid-ethanol hydrolysis - Jiahui Wang; Jiaqi Dou; Zixin Shu; Lele Li; Zhengyu Jin; Xing Zhou (Food Bioscience, 2024)

Assembly of 3D printed N-doped biochar as impeller with CaCO3 as sacrificial pore generator for enhanced dye adsorption - Zining Zhou; Kaiji Xu; Changyong Li; Jianbin Lin; Juanjuan Bian; Kang Sun; Jianchun Jiang; Shu-Feng Zhou; Guowu Zhan (Chemical Engineering Journal, 2024)

UV light absorption at 370 nm by mineral dust, organic carbon, and elemental carbon in the Himalayas and Tibetan Plateau - Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Hong Huang; Ting Zhang; Xiao-Li Su; Jun-Ji Cao (Atmospheric Environment, 2024)

Multi-agent mobile networking observation experiment at the air-sea interface of ocean eddy - Yi Zhang; Dongxiao Wang; Li Zhou; Chunhua Qiu; Yunfei Zhang; Zhiliang Deng; Biao Zhang; Yunping Liu; Yeqiang Shu; Fenghua Zhou; Danian Liu; Zhengqiu Zhang (Science China Earth Sciences, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Impact of telomere length and mitochondrial DNA copy number variants on survival of newborn cloned calves - Liwen Bao; Yiye Zhou; Juan Shu; Hua Li; Shubin Xi; Miao Xu; Qin Cai; Xiuqin Dai; Yitao Zeng; Fanyi Zeng (Theriogenology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Targeted discovery of unusual diterpenoids with anti-fungal activity from the root of Euphorbia lathyris - Yiwei Wang; Shu Xu; Guodong Zhang; Pirui Li; Chenyang Liu; Jiarui Zhou; Xu Feng; Linwei Li; Yu Chen (Phytochemistry, 2024)

Selenium alleviates chromium stress and promotes chromium uptake in As-hyperaccumulator Pteris vittata: Cr reduction and cellar distribution - Qian-Yu Zhou; Wei Li; Si-Xue He; Song-Ge Deng; Shu-Fen Xiao; Chen-Jing Liu; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Foliar-selenium enhances plant growth and arsenic accumulation in As-hyperaccumulator Pteris vittata: Critical roles of GSH-GSSG cycle and arsenite antiporters PvACR3 - Wei Li; Si-Xue He; Qian-Yu Zhou; Zhi-Hua Dai; Chen-Jing Liu; Shu-Fen Xiao; Song-Ge Deng; Lena Q. Ma (Journal of Hazardous Materials, 2024)

Nano- and microplastics drive the dynamic equilibrium of amoeba-associated bacteria and antibiotic resistance genes - Min Zhou; Lu Ma; Zihe Wang; Shicheng Li; Yijun Cai; Meicheng Li; Lin Zhang; Cheng Wang; Bo Wu; Qingyun Yan; Zhili He; Longfei Shu (Journal of Hazardous Materials, 2024)

A novel synthesized Vanillin-Based Deep Eutectic Agent (V-DEA) mitigates postharvest fungal decay and improve shelf life and quality of cherry tomatoes - Hafiz Umer Javed; Nuwan D. Kularathnage; Jiaxiu Du; Ruofan Liu; Zhiqing Yang; Sixia Zhong; Jiajie Zhou; Muzammil Hussain; Xugang Shu; Li-Yan Zeng (Food Chemistry, 2024)

Solution-processable organic–inorganic materials with colorful afterglow at room temperature - Sheng-Hua Li; Tuo-Yu Zhou; Shu-Yue Yang; Tai-Wen Li; Penglin Zhang; Guang-Yue Li; Chang Li; Hong-Qiao Li; Jing-Yi Li; Qian Zhao (Chemical Engineering Journal, 2024)

Correction: FTY720 Inhibits MPP+-Induced Microglial Activation by Affecting NLRP3 Inflammasome Activation - Shu Yao; Longjun Li; Xin Sun; Jun Hua; Keqi Zhang; Li Hao; Lixin Liu; Dongyan Shi; Hong Zhou (Journal of Neuroimmune Pharmacology, 2024)

Increasing structure diversity of farnesylated chalcones by a fungal aromatic prenyltransferase - Ying Wu; Shiyunhua Qian; Xiang Zhou; Shu-Ming Li; Chun-Mao Yuan; Song Yang; Kang Zhou (Phytochemistry, 2024)

Research on regional economic development and natural disaster risk assessment under the goal of carbon peak and carbon neutrality: A case study in Chengdu-Chongqing economic circle - Xin Zhang; Hao Luo; Xiaoyu Zeng; Chenyi Zhou; Zhile Shu; Huayun Li; Zheng Fei; Guichuan Liu (Land Use Policy, 2024)

Exploring the novel benefits of leucine: Protecting nitrite-induced liver damage in sub-adult grass carp (Ctenopharyngodon idella) through regulating mitochondria quality control - Lu-Lu Zhen; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Xiao-Qiu Zhou (Fish & Shellfish Immunology, 2024)

pH-dependent growth of alumina nanorods with a high aspect ratio for enhanced propane dehydrogenation performance - Haowei Wang; Wen-Cui Li; Ying Ma; Yu Zhang; Shu-Zhen Zhou; An-Hui Lu (Chemical Engineering Journal, 2024)

An aeration requirements calculating method based on BOD5 soft measurement model using deep learning and improved coati optimization algorithm - Wangben Zhao; Yuling Liu; Xing Zhou; Shuaishuai Li; Chenxu Zhao; Chuanchuan Dou; Hao Shu (Journal of Water Process Engineering, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Multiaxial yield behavior of 2D re-entrant auxetic cellular materials - Buyun Su; Zhiwei Zhou; Ji Qiu; XiaoHu Yao; Zhiqiang Li; Zhihua Wang; Xuefeng Shu (Engineering Structures, 2024)

Spatial heterogeneity and temporal tendency of channeled snow avalanche activity retrieved from Landsat images in the maritime snow climate of the Parlung Tsangpo catchment, southeastern Tibet - Hong Wen; Xiyong Wu; Xiaoyan Shu; Dong Wang; Siyuan Zhao; Guiyu Zhou; Xiaoning Li (Cold Regions Science and Technology, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

High-valent metal-oxo species transformation and regulation by co-existing chloride: Reaction pathways and impacts on the generation of chlorinated by-products - Hongyu Zhou; Yong-li He; Jiali Peng; Xiaoguang Duan; Xiaohui Lu; Heng Zhang; Yang Liu; Chuan-shu He; Zhaokun Xiong; Tianyi Ma; Shaobin Wang; Bo Lai (Water Research, 2024)

Short-term electrochemical stimulation induces sustained enhancement of extracellular pollutant degradation in anaerobic granular sludge - Liang Cheng; Shu-Na Li; Xiang-Tong Zhou; Xiang Xiao; Yang-Yang Yu (Journal of Water Process Engineering, 2024)

Fabrication and performance of MEA/DEA/TEA modified UiO-66 material for removing low concentration hydrogen sulfide at normal temperature environment - Gang Zhou; Siao Yang; Huiyun Sun; Guanshuang Chen; Xiuhui Qu; Shu Li; Xiaosu Dong (Fuel, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

Polypeptide urea increases rice yield and nitrogen use efficiency through root growth improvement - Shuang Liao; Fei Deng; Wei Zhou; Li Wang; Wu Li; Hui Hu; Shi-lin Pu; Shu-xian Li; Yong Chen; You-feng Tao; Chi Zhang; Qiu-ping Li; et al. (Field Crops Research, 2024)

Preparation and moisture transport behavior of multilevel branching network nanofiber membrane: Based on the Lattice Boltzmann method and inspired by plant transpiration - Gang Zhou; Qunzhi Meng; Xiuhui Qu; Rulin Liu; Shu Li; Xiaochuan Li; Yongmei Wang; Ziyuan Fang; Yanan Miao (Chemical Engineering Journal, 2024)

Effects of emission reductions on major anthropogenic aerosol-radiation-cloud interactions in East Asia in winter during 2007–2020 - Yaxin Hu; Bingliang Zhuang; Yinan Zhou; Yiman Gao; Peng Gao; Tijian Wang; Shu Li; Min Xie; Mengmeng Li (Atmospheric Environment, 2024)

Characteristics of urban black carbon aerosols in the Yangtze River Delta of China based on long-term observations - Yinan Zhou; Bingliang Zhuang; Tijian Wang; Peng Gao; Shu Li; Yaxin Hu; Mengmeng Li; Heng Cao; Min Xie; Huimin Chen (Atmospheric Environment, 2024)

Monitoring Yanwan deep-seated toppling deformation with the impact of water-level fluctuation by SAR observations - Kaiyu Ren; Renjiang Li; Xin Yao; Xiaoming Zhao; Li Ma; Chuangchuang Yao; Shu Jiang; Zhenkui Gu; Zhenkai Zhou (Landslides, 2024)

Analysis of the factors causing degradation and changes in the colourful pool area of the Huanglong travertine in Sichuan Province, China - ZiJian Zhou; FuDong Wang; YuYin Zhu; WuYang He; FaQin Dong; Shu Tang; QingMing Zhang; LiPing Jiang; GuoQing Huang; XueQin Zhao; JunHao Li; Shi Chen; et al. (Carbonates and Evaporites, 2024)

Mobilization and transformation of antimony in stibnite by microbial induced oxidation in mining environment - Shu Li; Guofang Pan; Xiaoqian Li; Aiguo Zhou; Ningjie He (Applied Geochemistry, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Mechanically treated Mn2O3 triggers peracetic acid activation for superior non-radical oxidation of micropollutants: Identification of reactive complexes - Yudan Dong; Chuan-Shu He; Si Sun; Jiali Liu; Zhi-Hui Xie; Jie-Yuan Li; Peng Zhou; Heng Zhang; Fan Dong; Bo Lai (Water Research, 2024)

Rhodopseudomonas palustris shapes bacterial community, reduces Cd bioavailability in Cd contaminated flooding paddy soil, and improves rice performance - Yanqiu Su; Qiuyun Shi; Ziyuan Li; Hongmei Deng; Qian Zhou; Lihuan Li; Lanyin Zhao; Shu Yuan; Qi Liu; Yanger Chen (Science of The Total Environment, 2024)

BambooBase: A comprehensive database of bamboo omics and systematics - Yun-Long Liu; Shu-Yang Gao; Guihua Jin; Meng-Yuan Zhou; Qijuan Gao; Cen Guo; Yi-Zhou Yang; Liang-Zhong Niu; Enhua Xia; Zhen-Hua Guo; Peng-Fei Ma; De-Zhu Li (Molecular Plant, 2024)

Spatio-temporal patterns of intense tropical cyclones in the Western North Pacific over the past 1600 years - Liang Zhou; Rumeng Hao; Mingchen Li; Yan Su; Shu Gao; Yang Yang; Zhixiong Shen; Jianjun Jia; Ya Ping Wang (Marine Geology, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

Maintenance of callus-associated endophyte balance to mitigate oxidative browning in plant tissue culture practices - Yu-Tao Wang; Chun-Xiao Chen; Ping Zhou; Chun-Xi Lu; Yun Wen; Yu Li; Xiao-Xia Pan; Shu-Sheng Zhu; Ming-Zhi Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Label compliance for ingredient verification: regulations, approaches, and trends for testing botanical products marketed for “immune health” in the United States - Hong You; Evelyn J. Abraham; Jason Mulligan; Yucheng Zhou; Maureen Montoya; Jennifer Willig; Bo-Kai Chen; Chin-Kun Wang; Li-Shu Wang; Athena Dong; Mark Shamtsyan; Haiuyen Nguyen; et al. (Critical Reviews in Food Science and Nutrition, 2024)

The emerging role of zinc on alleviating inflammatory responses and enhancing immunity in grass carp (Ctenopharyngodon idella) - Xin Zeng; Zheng-Xing Song; Xiao-Qiu Zhou; Wei-Dan Jiang; Pei Wu; Yang Liu; Ling Tang; Shu-Wei Li; Juan Yang; Lin Feng (Aquaculture, 2024)

Research on automatic recognition of active landslides using InSAR deformation under digital morphology: A case study of the Baihetan reservoir, China - Yang Liu; Xin Yao; Zhenkui Gu; Renjiang Li; Zhenkai Zhou; Xinghong Liu; Shu Jiang; Chuangchuang Yao; Shangfei Wei (Remote Sensing of Environment, 2024)

Modulating electron density enable efficient cascade conversion from peroxymonosulfate to superoxide radical driven by electron-rich/poor dual sites - Jingjing Jiang; Donglong Shi; Shu Niu; Shengda Liu; Yansong Liu; Bowen Zhao; Yanan Zhang; Hongyu Liu; Zhenhao Zhao; Mingyu Li; Mingxin Huo; Dandan Zhou; et al. (Journal of Hazardous Materials, 2024)

Disruption of intestinal epithelial permeability in the Co-culture system of Caco-2/HT29-MTX cells exposed individually or simultaneously to acrylamide and ochratoxin A - Jiawen Lu; Dan Su; Ying Yang; Mengni Shu; Yuting Wang; Xingtao Zhou; Qiang Yu; Chang Li; Jianhua Xie; Yi Chen (Food and Chemical Toxicology, 2024)

Structure-induced interfacial activation convoying the CO-relayed conversion of CO2 to dimethyl carbonate - Shu-Guo Han; Shenghua Zhou; Xiaofang Li; Jianqiang Zhao; Wen-Bo Wei; Lirong Zheng; Dong-Dong Ma; Xin-Tao Wu; Qi-Long Zhu (Chemical Engineering Journal, 2024)

Polycyclic aromatic compounds (PACs) in industrial soils from northwestern of China: occurrence, distribution, exposure risk, and implications on risk-based controls - Yousong Zhou; Kai Xiao; Yongqiang Zhang; Donglei Fu; Ke Jiang; Jinmu Luo; Yuancheng Li; Guofeng Shen; Wenxin Liu; Shu Tao; Senlin Lu (Environmental Geochemistry and Health, 2024)

Orbital-paced silicate weathering intensity and climate evolution across the Eocene-Oligocene transition in the southeastern margin of the Tibetan Plateau - He Tang; Hao Cui; Shu-Feng Li; Robert A. Spicer; Shi-Hu Li; Tao Su; Zhe-Kun Zhou; Caitlyn R. Witkowski; Vittoria Lauretano; Gang-Jian Wei (Global and Planetary Change, 2024)

High resolution osteoclast-targeted imaging-guided osteoporosis alleviation via persistent luminescence nanocomposite - Xiao Lin; Kewen Zhang; Yang Li; Fang Nan; Jun Li; Hui Zhang; Wei Deng; Weihang Ding; Kaixuan Li; Nur Jarhen; Yitong Zhou; Xiao Yu; et al. (Chemical Engineering Journal, 2024)

The application of human-derived cell lines in neurotoxicity studies of environmental pollutants - Ming-Rui Li; Shu-Hui Men; Zi-Ye Wang; Chen Liu; Guo-Rui Zhou; Zhen-Guang Yan (Science of The Total Environment, 2024)

Four pairs of neolignan enantiomers with distinctive isochroman moiety from the fruits of Crataegus pinnatifida and their protective activities against H2O2-induced SH-SY5Y cells - Peng Zhao; Shi-Fang Li; Jiao-Yang Hou; Shu-Yan Qin; Jia-Yi Li; Xiao-Fang Zhou; Xuan Liu; Jin-Le Hao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Analytical modelling of desiccation crack depth estimation for granitic soils - Yujie Wei; Shu Zhang; Yong Zhang; Xiaoquan Zhou; Zhongshan Dai; Hao Zheng; Zhaoxia Li; Chongfa Cai (Journal of Hydrology, 2024)

Long-term seawall barriers lead to the formation of an urban coastal lagoon with increased antibiotic resistome - Shu-Yi-Dan Zhou; Kai Yang; Roy Neilson; Hu Li; Hong-Zhe Li; Yan-Yan Zhou; Juxiu Liu; Jian-Qiang Su; Fu-Yi Huang (Journal of Environmental Management, 2024)

Anthropogenically and meteorologically modulated summertime ozone trends and their health implications since China's clean air actions - Dan Yan; Zhipeng Jin; Yiting Zhou; Mengmeng Li; Zihan Zhang; Tijian Wang; Bingliang Zhuang; Shu Li; Min Xie (Environmental Pollution, 2024)

Wearable electrochemical glucose sensor of high flexibility and sensitivity using novel mushroom-like gold nanowires decorated bendable stainless steel wire sieve - Fan Zhou; Shu Liu; Yimei Tang; Wenqiang Li; Lixin Hai; Xinmiao Zhang; Yan Li; Feng Gao (Analytica Chimica Acta, 2024)

Blue carbon in sediment from Sanggou Bay: composition, burial flux and its response to human activities - Shu Yang; Qian Yang; Xianli Song; Wei Zhou; Jihua Liu; Xiandong Qi; Junfeng Chen; Jun Huang; Bin Li; Yao Sun (Frontiers in Marine Science, 2024)
Marine primary production and terrestrial input are the main sources of buried carbon in sediments of marginal seas. Only marine-source carbon buried in sediments, fixed and stored by marine ecosystems, belongs to “blue carbon” and reflects marine ecosystems’ carbon sink function. The pattern of buried blue carbon in sediments, its flux, and its relationship with environmental changes remain unclear. The study aimed to investigate the composition of blue carbon in the sediments of Sanggou Bay, a special type of marginal sea. The analysis of sediment carbon sources was conducted through the C/N ratio and microscopic examination. The study also examined the long-term changes in the blue carbon burial fluxes. Results showed Blue carbon, which is sea-sourced carbon, accounted for about 23% of the total carbon content and its concentration ranged from 0.17% to 0.51%, with an average of about 0.25% ± 0.10%. The content of organic blue carbon in this sea area ranges from 0.09% to 0.26%, with an average of around 0.18% ± 0.04%. It constitutes approximately 72% of the buried blue carbon in the sediment, making it the primary component of buried blue carbon. Meanwhile, the content of inorganic blue carbon ranges from 0.01% to 0.32%. Over the past 70 years, the burial fluxes of sedimentary blue carbon, organic blue carbon and inorganic blue carbon in the Sanggou Bay are about 0.54 ± 0.22 mmol/(cm 2 a), 0.38 ± 0.07 mmol/(cm 2 a) and 0.17 ± 0.22 mmol/(cm 2 a), respectively; their long-term changes have been significantly affected by human aquaculture activities. Large-scale raft-rack aquaculture activities have caused a reduction in water flow velocity and an increase in the deposition of particulate organic matter, which in turn has led to the burial of organic blue carbon in the sediment. Additionally, the competition between aquaculture products and small calcareous organisms, such as mussels, foraminifera, may have inhibited the growth of small calcareous organisms. We suggest this has resulted in reduced burial fluxes of inorganic blue carbon and a decrease in its proportion among total blue carbon in the sea area. Our findings imply that aquaculture activities in Sanggou Bay had a negative impact on the burial of blue carbon in the sediments.

Antioxidant analysis of flavonoids extracted from Artemisia argyi leaf and their antibacterial activities against food-borne pathogens Escherichia coli and Staphylococcus aureus - Zichao Wang; Xueyan Zhou; He Chang; Zhihan Shu; Haiqin Gou; Yi Zheng; Yanhui Yang; Yahui Yang; Qi Wang; Na Li (Biologia, 2024)

Two new anthraquinone derivatives from Saprosma crassipes H. S. Lo - Xin-Shu Ji; De-Cai Dai; Yi-Tong Wang; Jing-Yi Cui; Hai-Xiang Li; Xin-Ming Song; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

Sesquiterpenoids from aged Artemisia argyi and their 3D-QSAR for anti-HBV activity - Yu-Ying Song; Yong-Zhi Zhou; Yun-Fen Wang; Teng-Yun Shu; Yang Feng; Min Xu; Li-Hua Su; Hai-Zhou Li (Phytochemistry, 2024)

Monsoon influence on plant diversity in northern Indochina: Evidence from the late Miocene Yen Bai flora, northern Vietnam - Hung Ba Nguyen; Jian Huang; Truong Van Do; Hoa Mai Thi Nguyen; Shu-Feng Li; Minh Trung Nguyen; Hung Dinh Doan; Zhe-Kun Zhou; Robert A. Spicer; Tao Su (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Mixed cropping enhances the nitrogen and phosphorus purification efficiency of sewage in wetland ecosystems - Jiancong Zhang; Hongtao Si; Yunqi Wang; Renhua Li; Shu Li; Lijun Zhou; Yujie Wang; Lintao Wang; Le Yin; Hongshan Zhang (Journal of Water Process Engineering, 2024)

Investigation of bacterial diversity from hybrid water sources to multiple terminal sites on an isolated island in the south China sea - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Yi Wang; Shu-Jun Yang; Jie Kong; Ying-Li Zhou; Jun-Lin Hu; Ke Ding; Si Zhang (Journal of Cleaner Production, 2024)

Ecological zoning and dynamic assessment of effectiveness in the Three Gorges Reservoir Area, China - Yuqi Xie; Shu Wang; Shujiang Xiang; Zifang Wang; Yanyun Li; Zhongshu Wang; Mi Zhou; Ying Wang; Ming Gao (Ecological Modelling, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Disrupted topological organization of functional brain networks in traumatic axonal injury - Jian Li; Yongqiang Shu; Liting Chen; Bo Wang; Linglong Chen; Jie Zhan; Hongmei Kuang; Guojin Xia; Fuqing Zhou; Honghan Gong; Xianjun Zeng (Brain Imaging and Behavior, 2023)
Traumatic axonal injury (TAI) may result in the disruption of brain functional networks and is strongly associated with cognitive impairment. However, the neural mechanisms affecting the neurocognitive function after TAI remain to be elucidated. We collected the resting-state functional magnetic resonance imaging data from 28 patients with TAI and 28 matched healthy controls. An automated anatomical labeling atlas was used to construct a functional brain connectome. We utilized a graph theoretical approach to investigate the alterations in global and regional network topologies, and network-based statistics analysis was utilized to localize the connected networks more precisely. The current study revealed that patients with TAI and healthy controls both showed a typical small-world topology of the functional brain networks. However, patients with TAI exhibited a significantly lower local efficiency compared to healthy controls, whereas no significant difference emerged in other small-world properties (Cp, Lp, γ, λ, and σ) and global efficiency. Moreover, patients with TAI exhibited aberrant nodal centralities in some regions, including the frontal lobes, parietal lobes, caudate nucleus, and cerebellum bilaterally, and right olfactory cortex. The network-based statistics results showed alterations in the long-distance functional connections in the subnetwork in patients with TAI, involving these brain regions with significantly altered nodal centralities. These alterations suggest that brain networks of individuals with TAI present aberrant topological attributes that are associated with cognitive impairment, which could be potential biomarkers for predicting cognitive dysfunction and help understanding the neuropathological mechanisms in patients with TAI.

Establishment of a tilapia lake virus (TiLV)-susceptible cell line for anti-TiLV Chinese herbal compound screening - Song Zhu; Bo Miao; Yu-Zhou Zhang; Qin Yang; Xun-Teng Deng; Li-Hong Gao; Ji-Shu Zheng; De-Cheng Pu; De-Shou Wang; Sheng-Qi Su (Aquaculture, 2023)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Himalaya to Hengduan: dynamics of alpine treelines under climate change - Achyut Tiwari; Arjun Adhikari; Ze-Xin Fan; Shu-Feng Li; Alistair S. Jump; Zhe-Kun Zhou (Regional Environmental Change, 2023)

Disentangling in-vivo microstructural changes of white and gray matter in mild cognitive impairment and Alzheimer’s disease: a systematic review and meta-analysis - Shuchang Zhong; Jingjing Lou; Ke Ma; Zhenyu Shu; Lin Chen; Chao Li; Qing Ye; Liang Zhou; Ye Shen; Xiangming Ye; Jie Zhang (Brain Imaging and Behavior, 2023)

Deformation characteristics and mechanism of an impoundment-induced toppling landslide in Baihetan Reservoir based on multi-source remote sensing - Zhen-kai Zhou; Xin Yao; Ren-jiang Li; Shu Jiang; Xiao-ming Zhao; Kai-yu Ren; Yi-fei Zhu (Journal of Mountain Science, 2023)

Persulfate enhanced removal of bisphenol A by copper oxide/reduced graphene oxide foam: Influencing factors, mechanism and degradation pathway - Qinwen Zhou; Lijun Luo; Lihong Xia; Canhu Cha; Fengzhi Jiang; Hongbin Wang; Jianhui Dai; Li Shu (Chemosphere, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Pogocablenes A-O, fifteen undescribed sesquiterpenoids with structural diversity from Pogostemon cablin - Shu-Yi Li; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Lu Su; Dan Liu; Hong-Mei Li; Rong-Tao Li (Phytochemistry, 2023)

Construction of continuous flow catalytic reactor-HPLC system with ultrahigh catalytic activity using 2D nanoflower MOF-derived Cu2O/Cu/PDA/CF catalyst - Yan Li; Shuang Zheng; Shenghuai Hou; Tiantian Chen; Yuxuan Bai; Manlin Zhang; Dandan Zhou; Shu Yang; Hui Xu; Ganbing Zhang (Journal of Hazardous Materials, 2023)

Chalcogen-modified copper-nitrogen co-doped carbon as a stable and efficient antimicrobial cathode catalyst for microbial fuel cells - Bi-Lin Lai; Hai-Xia Liao; Shu-Qi Zhou; Hui-Xu Wei; Ai-Yi Li; Nan Li; Zhao-Qing Liu (Journal of Environmental Chemical Engineering, 2023)

Participation influence of silicate on the temporal and spatial distribution of chloride electromigration in the electrokinetics of municipal solid waste incineration fly ashes - Tao Huang; Lulu Zhou; Jiajie Yao; Shu-wen Zhang; Haiyan Li (Journal of Environmental Chemical Engineering, 2023)

Experimental study on interlayer interference effect of CBM commingled production in a multi-pressure system under output control mode - Qixian Li; Longyong Shu; Jiang Xu; Shoujian Peng; Fazhi Yan; Zhonggang Huo; Du Liu; Chao Li; Bin Zhou (Fuel, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Enhanced retention of surface-adsorbed atomic hydrogen through sulfidation of nano zerovalent iron for water decontamination - Guan-Nan Zhou; Jia-Qi Chen; Wen-Qiang Li; Chuan-Shu He; Li Gong; Xiao-Cheng Liu; Yi-Ran Wang; Dahong Huang; Yang Mu (Chemical Engineering Journal, 2023)

An all-in-one enzymatic DNA network based on catalytic hairpin assembly for label-free and highly sensitive detection of APE1 - Shaoying Zhou; Xingrong Li; Xiaojia Shu; Xiaoying Cai; Haiping Wu; Shijia Ding; Yurong Yan (Analytica Chimica Acta, 2023)

Strong succession in prokaryotic association networks and community assembly mechanisms in an acid mine drainage-impacted riverine ecosystem - Mengmeng Wang; Xiaonan Wang; Sining Zhou; Zifeng Chen; Mengyun Chen; Shiwei Feng; Jintian Li; Wensheng Shu; Baichuan Cao (Water Research, 2023)

A cytochrome P450 system initiates 4-nitroanisole degradation in Rhodococcus sp. strain JS3073 - Shu-Ting Zhang; Tao Li; Shi-Kai Deng; Jim C. Spain; Ning-Yi Zhou (Journal of Hazardous Materials, 2023)

High-energy and dendrite-free solid-state zinc metal battery enabled by a dual-network and water-confinement hydrogel electrolyte - Zhenglin Li; Guoqiang Zhou; Lei Ye; Jinyu He; Wangwang Xu; Shu Hong; Weimin Chen; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Chemical Engineering Journal, 2023)

Composites of TiO2 pillared sericite: Synthesis, characterization and photocatalytic degradation of methyl orange - Yu Liang; Wei Li; Baohui Bei; Chong Li; Zetian He; Xuan Wang; Run Zhou; Hao Ding; Shu Li (Applied Clay Science, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Accumulated plastic deformation behavior of granite residual soil under cyclic loading considering the influence of initial unloading - Rongjun Shu; Lingwei Kong; Tianguo Li; Tao Jian; Zhenhua Zhou (Transportation Geotechnics, 2023)

Germacrane-type sesquiterpenoids from the flowers of Chrysanthemum indicum with hepatoprotective activity - Yu Liu; Fei Zhou; Hong-Zhen Shu; Li-Gen Lin; Qing-Wen Zhang (Food and Chemical Toxicology, 2023)

Dietary zearalenone alters gill epithelial morphology and subsequent risk of infection: Insights from a freshwater grass carp (Ctenopharyngodon idella) model - Hong-Yun Zhang; Ya-Li Wang; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Hai-Feng Mi; Sheng-Yao Kuang; Ling Tang; Shu-wei Li; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Schisandrin B Improves the Hypothermic Preservation of Celsior Solution in Human Umbilical Cord Mesenchymal Stem Cells - Ying Zhang; Peng Wang; Mei-xian Jin; Ying-qi Zhou; Liang Ye; Xiao-juan Zhu; Hui-fang Li; Ming Zhou; Yang Li; Shao Li; Kang-yan Liang; Yi Wang; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Dynamic risk analysis of oil depot storage tank failure using a fuzzy Bayesian network model - Qing-Yun Zhou; Bei Li; Yi Lu; Jie Chen; Chi-Min Shu; Ming-shu Bi (Process Safety and Environmental Protection, 2023)

A unique suit of Wuchiapingian marine red beds in central China representing a specific paleogeography and paleoclimate association - Cheng Cheng; Zi'an Shan; Mingyu Shan; Zhonglai Zhou; Bingyan Ren; Yike Chu; Shuangying Li; Dan Wang; Hongzuo Wang; Xujie Shu; Peng Qian (Marine and Petroleum Geology, 2023)

Rejuvenation of the lithospheric mantle beneath the orogens: Constraints from elemental geochemistry and Os isotopes in mantle xenoliths - Sheng-Hua Zhou; Qiao Shu; D. Graham Pearson; Dongxu Li; Yong Xu; Jingao Liu (Geochimica et Cosmochimica Acta, 2023)

Screening of host gut-derived probiotics and effects of feeding probiotics on growth, immunity, and antioxidant enzyme activity of hybrid grouper (Epinephelus fuscoguttatus♀ × E. lanceolatus♂) - Yating Zhu; Wen Li; Mingqing Zhang; Zhongxuan Zhong; Zhiqian Zhou; Jiayi Han; Cuiping Zhang; Jinlin Yang; Yuxin Wu; Hu Shu (Fish & Shellfish Immunology, 2023)

Molecular mechanism of adsorbing triclocarban by the activated sludge in wastewater treatment systems - Hao Wang; Hanlin Cui; Xiaodan Ma; Carolyn R. Cornell; Liying Zhang; Yijun Ren; Minghan Li; Ying Liu; Shu-Hong Gao; Zhiling Li; Ai-Jie Wang; Jizhong Zhou; et al. (Chemical Engineering Journal, 2023)

Engineering triple internal electric fields in Ag NWs@BaTiO3 composites for ultrasonic-visible-light driven antibacterial activity - Guoqiang Shu; Yaqi Lin; Rui Zhong; Xiaofan Su; Shanhong Guo; Chao Wang; Changan Zhou; Lei Song; Li Xie; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Modeling the Operating Performance of a Drinking Water Biological Aerated Filter and the Formation of Organic Nitrogen - Jia Kang; Chu-qiong Song; Ning Zhou; Yao-wen Zhang; Shu-li Liu; Gang-fu Song; Wa-ni Zhou (Environmental Science and Pollution Research, 2023)

Hyperbranched polyethyleneimine-functionalised chitosan aerogel for highly efficient removal of melanoidins from wastewater - Jia-Yi Tang; Yan-Shu Xiong; Ming-Xing Li; Ran Jia; Li-Shu Zhou; Bo-Huan Fan; Kai Li; Wen Li; Hong Li; Hai-Qin Lu (Journal of Hazardous Materials, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

Ganoderma lucidum extract promotes tumor cell pyroptosis and inhibits metastasis in breast cancer - Chunlian Zhong; Yumei Li; Wulin Li; Shu lian; Ye Li; Changhui Wu; Kun Zhang; Guiyu Zhou; Weiyu Wang; Huo Xu; Mingqing Huang; Vladimir Katanaev; et al. (Food and Chemical Toxicology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Genome-wide identification, structural and evolutionary characteristics, and expression analysis of aquaporin gene family members in Mercenaria mercenaria - Cong Zhou; Zhi-shu Lin; Ying Shi; Jie Feng; Zhi Hu; Mei-jie Yang; Pu Shi; Yong-ren Li; Yong-jun Guo; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
Aquaporins (AQPs) are highly-selective transmembrane water transporters that are involved in the adaptation to environmental challenges. However, the structure, function, and evolution of AQPs in bivalves remain largely unknown. In this study, AQP gene family members were identified in nine bivalve species, and their abundance rangs from 7 to 15. Nine AQPs (MmAQPs) were identified in the genome of hard clam ( Mercenaria mercenaria ), which is a euryhaline bivalve that has evolved sophisticated osmoregulatory mechanisms and salinity adaptation. Structurally, all MmAQPs contain 6 or 12 transmembrane α-helices, a major intrinsic protein (MIP) domain, and 2 asparagine-proline-alanine (NPA) motifs. MmAQPs were classified into three subfamilies based on phylogenetic analysis: AQP1-like, AQP3-like, and AQP8-like. No AQP11-like subfamily member was identified in the genome of hard clam. Tandem duplication resulted in a lineage-specific expansion in AQP8-like subfamily in hard clams. MmAQP8 genes showed different expression sensitivity to different environmental stressors. The gene expression patterns of three MmAQP8 were similar under heat, hypoxia, and air exposure stress, but differed greatly under salinity stress, indicating that tandem duplication events may accelerate the functional divergence of AQP8 genes in hard clams. AQP3-like members may have undergone gene loss during evolution, resulting in weakened glycerol and urea penetration in hard clams. Three orthologs of MmAQPs were detected in the genomes of Cyclina sinensis and Archivesica marissinica through synteny analyses. Tissue expression profiles showed that MmAQP genes were highly expressed in the foot and hepatopancreas. Under environmental stress, the expression levels of most of the MmAQP genes changed significantly to maintain metabolic homeostasis. Several MmAQP genes were downregulated to reduce water permeability under salinity and air exposure stress. Several MmAQP genes were significantly upregulated to promote the transmembrane transport of ammonia and reactive oxygen species and activate anti-apoptotic responses to resist stress. This study provides a comprehensive understanding of the AQP gene family in hard clams, and lays a foundation for further studies to explore the functions of AQPs in bivalves.

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Waste bamboo framework decorated with α-FeOOH nanoneedles for effective arsenic (V/III) removal - Lina Xu; Zhu Shu; Jingyang Song; Tiantian Li; Jun Zhou (Science of The Total Environment, 2023)

Associations between trace level thallium and multiple health effects in rural areas: Chinese Exposure and Response Mapping Program (CERMP) - Yun-Jiang Yu; Zhen-Chi Li; Yang Zhou; Chen-Yin Dong; Hong-Xuan Kuang; Tong Zheng; Ming-Deng Xiang; Xi-Chao Chen; Hong-Yan Li; Xiao-Wen Zeng; Shu-Li Xu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Structural characterization and anti-inflammatory effects of an arabinan isolated from Rehmannia glutinosa Libosch. - Han Zhang; Yimin Yue; Qian Zhang; Lanyuan Liang; Chuanqiu Li; Ying Chen; Wei Li; Mingming Peng; Mengru Yang; Mantong Zhao; Xia Cao; Luyang Zhong; et al. (Carbohydrate Polymers, 2023)

The galU gene is required for in vivo survival of pseudomonas plecoglossicida in large yellow croaker ( Larimichthys crocea ) - Feng‐Ling Shu; Li‐Yun Jin; Hao Liu; Zhen Tao; Fei Yin; Jia‐Song Xie; Su‐Ming Zhou (Journal of Fish Diseases, 2023)
Pseudomonas plecoglossicida is an important pathogenic bacterium in aquaculture that causes visceral granulomas in large yellow croaker ( Larimichthys crocea ). Uridine diphosphate glucose phosphorylase encoded by galU plays a key role in biosynthesis of the bacterial envelope, particularly lipopolysaccharide and the capsule. In this study, we inactivated the galU gene in the P. plecoglossicida isolate XSDHY‐P. The galU mutant strain showed impaired growth in the early exponential stage and lacked the O polysaccharide side chain in lipopolysaccharide, but almost no defect in biofilm formation was detected. The galU mutant strain also exhibited significantly more sensitivity to the bactericidal action of normal fish serum mediated by the complement system compared to the wild‐type strain. In a cell model originating from the head kidney of large yellow croaker, the galU mutant strain showed lower capacities of adhesion, invasion, and intracellular survival compared to the wild‐type strain. In addition, the deficiency of the galU mutant drastically decreased bacterial loads in tissues and attenuated P. plecoglossicida virulence in fish. These results suggest that the galU gene of P. plecoglossicida is required for in vivo survival in large yellow croaker.

Applications of Polyaniline–Alkaline Copper Carbonate Composites for Anti-Bio-Attachment of Concrete in Marine Environments - Shaofei Zhou; Xu Liang; Jiandong Gao; Bo Ye; Chengyu Li; Jin Qian; Jiangtao Shu; Ying Ye (Journal of Marine Science and Engineering, 2023)
This study proposed the use of polyaniline–alkaline copper carbonate composites as anti-corrosion and anti-biofouling concrete additives and established a set of high-dispersion preparation methods for this composite additive. The effects of polyaniline–alkaline copper carbonate composites in concrete were investigated in marine environments via the preparation of concrete specimens, actual sea suspension experiments, concrete mechanical property tests, and biological attachment avoidance tests. The experimental results showed that (1) the yield of the chemical reactions leading to the preparation of the composite was above 96.46% with a good output. The composite was hydrophilic. The addition of ethylene carbonate as a surfactant and the mixing of the composite into the concrete in a suspension form enabled uniform dispersion of the composite. (2) In the sea waters of Zhoushan, China, bio-attachment was mainly dominated by barnacles and sea anemones. Polyaniline–alkaline copper carbonate composites had good anti-bio-attachment properties and could significantly reduce the amount of bio-attachment in concrete. (3) When the additive content was less than 0.20% of the concrete mass, it did not negatively affect the mechanical properties of the concrete specimens and exerted anti-corrosion and anti-biofouling effects. This reduced the strength loss of concrete and increased the service life of the concrete specimens in the ocean. To ensure the best application effect of the compound in concrete, the recommended content of the compound is 0.05–0.15% of the concrete mass.

Identification and pathogenetic study of tilapia lake virus (TiLV) isolated from naturally diseased tilapia - Tao He; Yu-Zhou Zhang; Li-Hong Gao; Bo Miao; Ji-Shu Zheng; De-Cheng Pu; Qing-Qing Zhang; Wei-Wei Zeng; De-Shou Wang; Sheng-Qi Su; Song Zhu (Aquaculture, 2023)

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Manure and biochar have limited effect on lettuce leaf endophyte resistome - Yan-Zi Wang; Shu-Yi-Dan Zhou; Xin-Yuan Zhou; Xin-Li An; Jian-Qiang Su (Science of The Total Environment, 2023)

Labdane diterpenoids from the heartwood of Leucosceptrum canum that impact on root growth and seed germination of Arabidopsis thaliana - Yan Liu; Yan-Ying Zhou; Shi-Hong Luo; Kai Guo; Man-Wen Zhang; Shu-Xi Jing; Chun-Huan Li; Juan Hua; Sheng-Hong Li (Phytochemistry, 2023)

Isolation and evaluation of antioxidants from Arisaema heterophyllum tubers - Na Sun; Huanhuan Yang; Miao Zhou; Yanyan Hou; Xinru Wu; Wenqian Li; Yifang Zhang; Jinge Sun; Xin Xiong; Jihong Huang; Penghua Shu (Phytochemistry Letters, 2023)

A water-gating and zinc-sieving lignocellulose nanofiber separator for dendrite-free rechargeable aqueous zinc ion battery - Zhenglin Li; Lei Ye; Guoqiang Zhou; Wangwang Xu; Kangning Zhao; Xiaoman Zhang; Shu Hong; Tongtong Ma; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Chemical Engineering Journal, 2023)

Paenibacillus alkalitolerans sp. nov., a bacterium isolated from a salt lake of Turpan City in Xinjiang Province, north-west China - Rui Li; Zhou-Tian-Le Zhang; Yun Wang; Gang-Qiang Jiang; Min Yin; Yu Li; Wen-Yong Zhu; Shu-Kun Tang (Folia Microbiologica, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Impaired intestinal physical barrier of on-growing grass carp by deficient iron under Aeromonas hydrophila infection - Yan-Lin Guo; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Shu-wei Li; Ling Tang; Lu Zhang; Haifeng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

City-scale distribution of airborne antibiotic resistance genes - Xin-Yuan Zhou; Hu Li; Shu-Yi-Dan Zhou; Yu-Sen Zhang; Jian-Qiang Su (Science of The Total Environment, 2023)

Pod fossils of Albizia (Fabaceae: Caesalpinioideae) from the late Miocene of northern Vietnam and their phytogeographic history - Hung Ba Nguyen; Jian Huang; Truong Van Do; Gaurav Srivastava; Hoa Mai Thi Nguyen; Shu-Feng Li; Lin-Lin Chen; Minh Trung Nguyen; Hung Dinh Doan; Zhe-Kun Zhou; Tao Su (Review of Palaeobotany and Palynology, 2023)

Dietary cinnamaldehyde improves muscle protein content by promoting muscle fiber growth via PTP1B/IGF1/PI3K/AKTs-TOR/FOXO3a signaling pathway in grass carp (Ctenopharyngodon idella) - Yang Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Yan Peng; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Reaction-kinetic model-guided biocatalyst engineering for dual-enzyme catalyzed bioreaction system - Feng Cheng; Sheng-Yi Zhou; Lu-Xin Chen; Wei Zhang; Shu-Fang Li; Chun-Yue Weng; Ya-Jun Wang; Yu-Guo Zheng (Chemical Engineering Journal, 2023)

c-kit+VEGFR-2+ Mesenchymal Stem Cells Differentiate into Cardiovascular Cells and Repair Infarcted Myocardium after Transplantation - Pei Zhou; Shu-na Yu; Hai-feng Zhang; Yong-li Wang; Ping Tao; Yu-zhen Tan; Hai-jie Wang (Stem Cell Reviews and Reports, 2023)
Resent study suggests that c-kit + cells in bone marrow-derived MSCs may differentiate toward cardiamyocytes. However, the properties of c-kit + MSCs remain unclear. This study isolated c-kit + VEGFR-2 + cells from rat bone marrow-derived MSCs, and assessed potential of c-kit + VEGFR-2 + MSCs to differentiate towards cardiovascular cells and their efficiency of repairing the infarcted myocardium after transplantation. Gene expression profile of the cells was analyzed with RNA-sequencing. Potential of differentiation of the cells was determined after induction. Rat models of myocardial infarction were established by ligation of the left anterior descending coronary artery. The cells were treated with hypoxia and serum deprivation for four hours before transplantation. Improvement of cardiac function and repair of the infarcted myocardium were assessed at four weeks after transplantation. Gene expression profile revealed that c-kit + VEGFR-2 + MSCs expressed most smooth muscle-specific and myocardium-specific genes, while expression of endothelium-specific genes was upregulated significantly. After induction with VEGF or TGF-β for two weeks, the cells expressed CD31 and α-SMA respectively. At three weeks, BMP-2-induced cells expressed cTnT. After transplantation of the cells, cardiac function was improved, scar size of the infarcted myocardium was decreased, and angiogenesis and myocardial regeneration were enhanced significantly. Moreover, paracrine in the myocardium was increased after transplantation. These results suggest that c-kit + VEGFR-2 + MSCs have a potential of differentiation towards cardiovascular cells. Transplantation of c-kit + VEGFR-2 + MSCs is effective for repair of the infarcted myocardium. c-kit + VEGFR-2 + MSCs may be a reliable source for cell therapy of ischaemic diseases. Graphical abstract

Correction: Essential oils from two aromatic plants repel the tobacco whitefly Bemisia tabaci - Shu Li; Hui Li; Qiong Zhou; Fan Zhang; Nicolas Desneux; Su Wang; Lei Shi (Journal of Pest Science, 2023)

Rapid quantitative study of check dam breach floods under extreme rainstorm - Qiang Zhang; Yanlong Li; Shu Yu; Lin Wang; Zuyu Chen; Jiawei Zhou (Natural Hazards, 2022)

Clinical and immune response characteristics among vaccinated persons infected with SARS-CoV-2 delta variant: a retrospective study - Cunjin Wang; Yong Li; Yuchen Pan; Luojing Zhou; Xi Zhang; Yan Wei; Fang Guo; Yusheng Shu; Ju Gao (Journal of Zhejiang University-SCIENCE B, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

3D displacement and deformation mechanism of deep-seated gravitational slope deformation revealed by InSAR: a case study in Wudongde Reservoir, Jinsha River - Kaiyu Ren; Xin Yao; Renjiang Li; Zhenkai Zhou; Chuangchuang Yao; Shu Jiang (Landslides, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Dyadobacter diqingensis sp. nov., isolated from Baima snow mountain of Diqing Tibetan Autonomous Prefecture in Yunnan province, south-west China - Lei Ran; Man Peng; Wei-Qun Wang; Yu-Zhou Feng; Juan Wang; Yu Wang; Cui-Ying Li; Xin-Xing Liu; Wei-Xun Chunyu; Shu-Kun Tang (Archives of Microbiology, 2022)

P2X7/P2X4 Receptors Mediate Proliferation and Migration of Retinal Microglia in Experimental Glaucoma in Mice - Meng-Xi Xu; Guo-Li Zhao; Xin Hu; Han Zhou; Shu-Ying Li; Fang Li; Yanying Miao; Bo Lei; Zhongfeng Wang (Neuroscience Bulletin, 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

Halomonas faecis sp. nov., a halophilic bacterium isolated from human faeces - Zhu-Xiang Liu; Jin-Hua Chen; Ling-Ling Yang; Yu-Zhou Feng; Li-Ying Deng; Jian-Wu He; Shu-Kun Tang; Yi-Guang Chen (Extremophiles, 2022)

Application of an improved hollow fiber liquid phase microextraction technique coupled to LC-MS/MS to studying migration of fluorescent whitening agents from plastic food contact materials - Wen-Li Zhou; Li Ding; Yun-Hui Cheng; Zhou Xu; Mao-Long Chen; Xian-Shu Fu (Food Additives & Contaminants: Part A, 2022)

A comprehensive comparison of data fusion approaches to multi-source precipitation observations: a case study in Sichuan province, China - Zhe Duan; Yufeng Ren; Xing Liu; Huike Lei; Xiaojun Hua; Xiaolong Shu; Li Zhou (Environmental Monitoring and Assessment, 2022)

Integrated Dynamics Response Analysis for IEA 10-MW Spar Floating Offshore Wind Turbine - Xiaojiang Guo; Yu Zhang; Jiatao Yan; Yiming Zhou; Shu Yan; Wei Shi; Xin Li (Journal of Marine Science and Engineering, 2022)
Wind energy in the deep-sea area is more abundant and the capacity of wind turbines can be made larger. Therefore, the research on deep-sea floating offshore wind turbines will be the primary strategy for wind energy exploitation in the future. The spar-type platform depends on the characteristics of a small water plane, deep draft, and good stability, which has been applied to the commercial development of deep-sea wind energy. In the next ten years, the 10-MW wind turbine will become the mainstream class installed in the floating offshore wind turbine farm. Thus, it is very necessary to conduct a comprehensive and in-depth study on the 10-MW spar type floating offshore wind turbine. The direct-drive 10-MW offshore wind turbine was proposed by the International Energy Agency (IEA) in Wind Task 37 in 2019. In this paper, a spar-type platform is designed to support the IEA 10-MW reference wind turbines, and a nonlinear aero-hydro-servo-elastic numerical model is established using the FAST tool (which is developed by the National Renewable Energy Laboratory, NREL). Then, the accuracy of the wind turbine and the sensitivity of the controller are verified, and the natural periods of the floating offshore wind turbine are obtained by free-decay tests. The natural periods of the platform in six degrees-of-freedom are found to be within the range recommended by the design standard. The measured wind and wave data of the target site close to Fujian Province of China are used to evaluate the performance of the floating offshore wind turbine under the 100-, 50-, 5-, and 2-year-return stochastic weather conditions. The results indicate that the design of the spar platform is reasonable and has excellent hydrodynamic performance.

A genetic-based population PK/PD modeling of methadone in Chinese opiate dependence patients - Dong Guo; Zhirong Tan; Xiaoya Lou; Shan Shi; Yan Shu; Honghao Zhou; Li Yu; Hong Yang (European Journal of Clinical Pharmacology, 2022)

Effects of synthetic nitrification inhibitor (3,4-dimethylpyrazole phosphate; DMPP) and biological nitrification inhibitor (methyl 3-(4-hydroxyphenyl) propionate; MHPP) on the gross N nitrification rate and ammonia oxidizers in two contrasting soils - Ting Lan; Mengxiao Li; Xiaoqian He; Ouping Deng; Wei Zhou; Ling Luo; Guangdeng Chen; Shu Yuan; Jing Ling; Min Zeng; Xuesong Gao (Biology and Fertility of Soils, 2022)

Epigenetic inactivation of ACAT1 promotes epithelial-mesenchymal transition of clear cell renal cell carcinoma - Peipei Han; Shu Wu; Limei Li; Danping Li; Jun Zhao; Haishan Zhang; Yifang Wang; Xuemin Zhong; Zhe Zhang; Ping Li; Liudmila Matskova; Xiaoying Zhou (Genes & Genomics, 2022)

Ecophysiological Responses of Five Mangrove Species (Bruguiera gymnorrhiza, Rhizophora stylosa, Aegiceras corniculatum, Avicennia marina, and Kandelia obovata) to Chilling Stress - Shu-Min Wang; You-Shao Wang; Bo-Yu Su; Yue-Yue Zhou; Li-Fang Chang; Xiao-Yu Ma; Xiao-Mei Li (Frontiers in Marine Science, 2022)
Although the low temperature is a critical growth constraint on plants, the physiological mechanism remains unclear, especially in mangrove plants. Hence, the morphological characteristics of five mangrove plants ( Bruguiera gymnorrhiza , Rhizophora stylosa , Aegiceras corniculatum , Avicennia marina , and Kandelia obovata ) were compared under chilling stress. The contents of hydrogen peroxide (H 2 O 2 ), malondialdehyde (MDA), and proline were tested. Activities of reactive oxygen species (ROS)-scavenging enzyme [superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT)] were also measured after chilling stress. It was concluded that K. obovata can well tolerate chilling stress, and B. gymnorrhiza suffered the most severe chilling damage. Leaf-morphology observation exhibited that K. obovata and A. corniculatum can sustain chilling stress, while B. gymnorrhiza wilted and A. marina turned brown. The content of H 2 O 2 increased at first and subsequently decreased in all plants. MDA increased instantaneously in B. gymnorrhiza and R. stylosa but changed slowly in K. obovata and A. corniculatum . The high content of proline accumulated in B. gymnorrhiza and K. obovata . The activities of the SOD, POD, and CAT increased at first and then decreased in all mangrove species. The antioxidants maintained high activity in K. obovata while decreasing earliest in A. marina exposed to the long-term chilling stress. Principal component analysis (PCA) indicated that high antioxidant enzyme activities play key roles in chilling tolerance for mangrove plants. The longer-term chilling tolerance of K. obovata may be related to the high antioxidant enzyme activities and proline accumulation. Lower H 2 O 2 and MDA contents strengthen the anti-chilling ability of A. corniculatum. Further investigation on the molecular mechanisms will facilitate the understanding of the anti-chilling ability of mangrove plants.

Essential oils from two aromatic plants repel the tobacco whitefly Bemisia tabaci - Shu Li; Hui Li; Qiong Zhou; Fan Zhang; Nicolas Desneux; Su Wang; Lei Shi (Journal of Pest Science, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

Overexpression of ORX or MCH Protects Neurological Function Against Ischemic Stroke - Gang Wu; Xi’an Zhang; Shijun Li; Dan Zhou; Jie Bai; Hanxiang Wang; Qing Shu (Neurotoxicity Research, 2022)

TP53-mediated miR-2861 promotes osteogenic differentiation of BMSCs by targeting Smad7 - Xian-Pei Zhou; Qi-Wei Li; Zi-Zhen Shu; Yang Liu (Molecular and Cellular Biochemistry, 2022)

Propioniciclava soli sp. nov., isolated from forest soil, Yunnan, China, and reclassification of the genus Brevilactibacter into the genus Propioniciclava, and Brevilactibacter sinopodophylli, Brevilactibacter flavus, and Brevilactibacter coleopterorum as Propioniciclava sinopodophylli comb. nov., Propioniciclava flava comb. nov., and Propioniciclava coleopterorum comb. nov., respectively - Le-Le Li; Jiang-Yuan Zhao; Yu Geng; Yu-Guang Zhou; Hui-Ren Yuan; Man Cai; Meng-Liang Wen; Ming-Gang Li; Shu-Kun Tang (Archives of Microbiology, 2022)

Kangiella shandongensis sp. nov., a novel species isolated from saltern in Yantai, China - Li-Yang Peng; Rui Yin; Shu-Kun Gao; Hui-Ning Jiang; Xiao-Xiao Liu; Yu Ma; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2022)

Triculata A, a novel compound from Tricyrtis maculata (D. Don) J. F. Macbr. with biological properties - Li Ren; Yun-Ze Wang; Wei Zhang; Rui Zhou; Ming Zhao; Zhi-Shu Tang; Jing Sun; Dong-Bo Zhang (Natural Product Research, 2021)

Halegenticoccus tardaugens sp. nov., an extremely halophilic archaeon isolated from a saline soil - Bing-Bing Liu; Nimaichand Salam; Shuang Cheng; Wen-qing Zhang; Yong-qing Zhou; Shu-xian Guo; Wen-Jun Li (Extremophiles, 2021)

Tracking historical storm records from high-barrier lagoon deposits on the southeastern coast of Hainan Island, China - Liang Zhou; Xiaomei Xu; Yaping Wang; Jianjun Jia; Yang Yang; Gaocong Li; Changliang Tong; Shu Gao (Acta Oceanologica Sinica, 2021)

Glycomyces salinus sp. nov., an actinomycete isolated from a hypersaline habitat - Rui Li; Gang-Qiang Jiang; Yun Wang; Yi-Guang Chen; En-Min Zhou; Shu-Kun Tang (Archives of Microbiology, 2021)

Association between large artery stenosis, cerebral small vessel disease and risk of ischemic stroke - Fei Han; Ding-Ding Zhang; Fei-Fei Zhai; Jun Xue; Jiang-Tao Zhang; Shuang Yan; Li-Xin Zhou; Jun Ni; Ming Yao; Meng Yang; Ming-Li Li; Zheng-Yu Jin; et al. (Science China Life Sciences, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

OSL chronology of a Palaeolithic site in a humid subtropical mountainous area of southeast China - Jian-hui Jin; Xiao-yang Wang; Zhen-yu Zhou; Yun-ming Huang; Xue-chun Fan; Xin-xin Zuo; Zhi-zhong Li; Zhi-yong Ling; Yong-qing Ren; Shu-tong Li (Journal of Mountain Science, 2021)

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Retrieval of sea surface temperature from the scanning microwave radiometer aboard HY-2B - Shu-Bo Liu; Xin-Dong Cui; Yi-Nan Li; Xu Jin; Wu Zhou; Hong-Xing Dang; Hao Li (International Journal of Remote Sensing, 2021)

Prevalence of maternally-inherited bacteria in native and invasive populations of the harlequin ladybird beetle Harmonia axyridis - Hongran Li; Xiaohan Shu; Ling Meng; Xuguo Zhou; John J. Obrycki; Baoping Li (Biological Invasions, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

The impact of ocean data assimilation on seasonal predictions based on the National Climate Center climate system model - Wei Zhou; Jinghui Li; Fanghua Xu; Yeqiang Shu; Yang Feng (Acta Oceanologica Sinica, 2021)

Mechanism of colluvial landslide induction by rainfall and slope construction: A case study - Zhou Zhou; Jun-hui Shen; Ying Li; Wei-feng Duan; Ri-chang Yang; Jun-cheng Shu; He-wei Li; Sheng-yu Tao; Sheng-zhe Zheng (Journal of Mountain Science, 2021)

Initial ingestion of CMV-infected plants reduces subsequent aphid performance - Xiao-bin Shi; Jun Deng; Zhuo Zhang; Shuo Yan; Li-min Zheng; Shu-e Sun; Yang Gao; Xu-guo Zhou; De-yong Zhang; Yong Liu (Arthropod-Plant Interactions, 2021)

Snapshot of the Pliocene environment of West Kunlun region, Northwest China - Jia Liu; Teng-Xiang Wang; Xin-Wen Zhang; Ai Song; Shu-Feng Li; Jian Huang; Teresa Spicer; Robert A. Spicer; Fei-Xiang Wu; Tao Su; Zhe-Kun Zhou (Palaeobiodiversity and Palaeoenvironments, 2021)

Seasonal rainfall patterns in stable carbon isotopes in the Mu Us Desert, northern China during the early and middle Holocene - Peixian Shu; Hong Wang; Weijian Zhou; Hong Ao; Dongfeng Niu; Xiaohao Wen; Baosheng Li (Climate Dynamics, 2021)

Transcription factor MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene MoAUH1 to govern infectious growth via mitochondrial fusion/fission balance in Magnaporthe oryzae - Yuhan Xiao; Luping Liu; Ting Zhang; Ruiwen Zhou; Yuan Ren; Xinrui Li; Haidong Shu; Wenwu Ye; Xiaobo Zheng; Zhengguang Zhang; Haifeng Zhang (Environmental Microbiology, 2021)
Summary Mitochondrial quality and quantity are essential for a cell to maintain normal cellular functions. Our previous study revealed that the transcription factor MoMsn2 plays important roles in the development and virulence of Magnaporthe oryzae . However, to date, no study has reported its underlying regulatory mechanism in phytopathogens. Here, we explored the downstream target genes of MoMsn2 using a chromatin immunoprecipitation sequencing (ChIP‐Seq) approach. In total, 332 target genes and five putative MoMsn2‐binding sites were identified. The 332 genes exhibited a diverse array of functions and the highly represented were genes involved in metabolic and catalytic processes. Based on the ChIP‐Seq data, we found that MoMsn2 plays a role in maintaining mitochondrial morphology, likely by targeting a number of mitochondria‐related genes. Further investigation revealed that MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene ( MoAUH1 ) to control mitochondrial morphology and mitophagy, which are critical for the infectious growth of the pathogen. Meanwhile, the deletion of MoAUH1 resulted in phenotypes similar to the Δ Momsn2 mutant in mitochondrial morphology, mitophagy and virulence. Overall, our results provide evidence for the regulatory mechanisms of MoMsn2, which targets MoAUH1 to modulate its transcript levels, thereby disturbing the mitochondrial fusion/fission balance. This ultimately affects the development and virulence of M . oryzae .

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

SUMOylation of Pdia3 exacerbates proinsulin misfolding and ER stress in pancreatic beta cells - Na Li; Xi Luo; Qilin Yu; Ping Yang; Zhishui Chen; Xinqiang Wang; Jipin Jiang; Jing Xu; Quan Gong; Decio L. Eizirik; Zhiguang Zhou; Jiajun Zhao; et al. (Journal of Molecular Medicine, 2020)

Correction to: Description of Paenibacillus yunnanensis sp. nov., Isolated from a Tepid Spring - Manik Prabhu Narsing Rao; Zhou-Yan Dong; S. Amoolya; Srujana Neelavar; Bing-Bing Liu; Shu-Xian Guo; Wael Hozzein; Wen-Jun Li (Current Microbiology, 2020)

Description of Paenibacillus yunnanensis sp. nov., Isolated from a Tepid Spring - Manik Prabhu Narsing Rao; Zhou-Yan Dong; S. Amoolya; Srujana Neelavar; Bing-Bing Liu; Shu-Xian Guo; Wael Hozzein; Wen-Jun Li (Current Microbiology, 2020)

Puerarin Alleviates Lipopolysaccharide-Induced Myocardial Fibrosis by Inhibiting PARP-1 to Prevent HMGB1-Mediated TLR4-NF-κB Signaling Pathway - Shu-Yuan Ni; Xing-Long Zhong; Ze-Hua Li; Dong-Jian Huang; Wen-Ting Xu; Yan Zhou; Cai-Wen Ou; Min-Sheng Chen (Cardiovascular Toxicology, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Naphthalene exerts non-target effects on the abundance of active fungi by stimulating basidiomycete abundance - Li-ying Lan; Li Zhang; Ya Shen; Jian Zhang; Wan-qin Yang; Zhen-feng Xu; Yang Liu; Shu-qin He; Wei Zhou; Han Li; Li-xia Wang; Si-ning Liu; et al. (Journal of Mountain Science, 2020)

Preparation of aluminum sludge composite gel spheres and adsorption of U(IV) from aqueous solution - Jin-hui Yang; Zeng-jiang Lei; Yang-hong Dai; Yi Luo; Shui-bo Xie; Jing-song Wang; Shu-kui Zhou; Bai Wei; Cong Li; Shi-qing Hu (Environmental Science and Pollution Research, 2020)

Genetic analysis and fine mapping of the gall midge resistance gene Gm5 in rice (Oryza sativa L.) - Hailian Zhou; Xinyi Wang; Yi Mo; Yang Li; Liuhui Yan; Zhihua Li; Wan Shu; Ling Cheng; Fengkuan Huang; Yongfu Qiu (Theoretical and Applied Genetics, 2020)

Discrimination of different sea ice types from CryoSat-2 satellite data using an Object-based Random Forest (ORF) - Su Shu; Xinghua Zhou; Xiaoyi Shen; Zhanchi Liu; Qiuhua Tang; Haili Li; Changqing Ke; Jie Li (Marine Geodesy, 2020)

Efficacy of internet-based integrated intervention on depression and anxiety symptoms in patients with COVID-19 - Ning Wei; Bo-chao Huang; Shao-jia Lu; Jian-bo Hu; Xiao-yi Zhou; Chan-chan Hu; Jing-kai Chen; Jin-wen Huang; Shu-guang Li; Zheng Wang; Dan-dan Wang; Yi Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Dialectical behavior therapy-based psychological intervention for woman in late pregnancy and early postpartum suffering from COVID-19: a case report - Jin-wen Huang; Xiao-yi Zhou; Shao-jia Lu; Yi Xu; Jian-bo Hu; Man-li Huang; Hua-fen Wang; Chan-chan Hu; Shu-guang Li; Jing-kai Chen; Zhong Wang; Shao-hua Hu; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Mechanisms of soil bacterial and fungal community assembly differ among and within islands - Pandeng Wang; Shao‐Peng Li; Xian Yang; Jizhong Zhou; Wensheng Shu; Lin Jiang (Environmental Microbiology, 2020)
Summary The study of islands has made substantial contributions to the development of evolutionary and ecological theory. However, we know little about microbial community assembly on islands. Using soil microbial data collected from 29 lake islands and nearby mainland, we examined the assembly mechanisms of soil bacterial and fungal communities among and within islands. We found that deterministic processes, especially homogeneous selection, tended to be more important in shaping the assembly of soil bacterial communities among islands, while stochastic processes tended to be more important within islands. Moreover, increasing island area increased the importance of homogeneous selection, but reduced the importance of variable selection, for soil bacterial community assembly within islands. By contrast, stochastic processes tended to dominate soil fungal community assembly both among and within islands, with dispersal limitation playing a more important role within than among islands. Our results highlight the scale‐ and taxon‐dependence of insular soil microbial community assembly, suggesting that spatial scale should be explicitly considered when evaluating the influences of habitat fragmentation on soil microbial communities.

Comparative genomics analysis of Nitriliruptoria reveals the genomic differences and salt adaptation strategies - Dai-Di Chen; Ye Tian; Jian-Yu Jiao; Xiao-Tong Zhang; Yong-Guang Zhang; Zhou-Yan Dong; Meng-Jie Xiong; Min Xiao; Wen-Sheng Shu; Wen-Jun Li (Extremophiles, 2020)

Evidence for the paternal mitochondrial DNA in the crucian carp-like fish lineage with hybrid origin - Shi Wang; Ni Jiao; Lu Zhao; Meiwen Zhang; Pei Zhou; Xuexue Huang; Fangzhou Hu; Conghui Yang; Yuqin Shu; Wuhui Li; Chun Zhang; Min Tao; et al. (Science China Life Sciences, 2020)

Long‐term variation in the abundance of Pacific herring ( Clupea pallasii ) from the Yellow Sea in the western North Pacific and its relation to climate over the past 590 years - Haoyu Li; Shu Yang; Qisheng Tang; Xin Zhou; Yao Sun (Fisheries Oceanography, 2020)
A qualitative understanding of the long‐term variation in the population dynamics of Yellow Sea (YS) herring is particularly important for clarifying the evolutionary processes and driving mechanisms of the YS large marine ecosystem. Unfortunately, because of a lack of long‐term, continuous, and simultaneous monitoring data, the specific driving processes and mechanisms of climate effects on the population dynamics of YS herring remain largely unknown. In response to this scientific issue, we preliminarily propose the idea of reconstructing long‐term changes in YS herring abundance over the past 590 years (AD 1417–2004) based on historical documents and attempt to explore the impacts of climate on the population. Our results show that YS herring abundance maintained at a relatively high level from AD 1417 to 1870 (during the Little Ice Age); in contrast, the population declined significantly from AD 1870 to 2004 at different rates. In addition, we also found that there were strong relationships between the population abundance of YS herring and the Pacific decadal oscillation (PDO) and drought/flood cycles. We suggest that the fluctuations in YS herring abundance may be influenced by ocean–climatic circulation shifts throughout the North Pacific, especially the PDO.

Paracetamol Degradation Performance and Mechanisms Using Microwave-Assisted Heat-Activated Persulfate in Solutions - Qi Zhang; Song Cheng; Hongying Xia; Libo Zhang; Junwen Zhou; Chunyang Li; Jianhua Shu; Xin Jiang (Water, Air, & Soil Pollution, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Correction to: Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Ya Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

FTY720 Inhibits MPP+-Induced Microglial Activation by Affecting NLRP3 Inflammasome Activation - Shu Yao; Longjun Li; Xin Sun; Jun Hua; Keqi Zhang; Li Hao; Lixin Liu; Dongyan Shi; Hong Zhou (Journal of Neuroimmune Pharmacology, 2019)

Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Yax Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Benzopyran derivatives from endophytic Daldinia eschscholzii JC-15 in Dendrobium chrysotoxum and their bioactivities - Ming Hu; Xue-Qiong Yang; Qing-Yan Zhou; Shu-Quan Li; Bang-Yan Wang; Bao-Hui Ruan; Ya-Bin Yang; Zhuo-Xi Zhang; Hao Zhou; Zhong-Tao Ding (Natural Product Research, 2019)

Effects of phosphorus on absorption and transport of selenium in rice seedlings - Ying Ying Li; Shu Hui Yu; Xin Bin Zhou (Environmental Science and Pollution Research, 2019)

Early identification and dynamic processes of ridge-top rockslides: implications from the Su Village landslide in Suichang County, Zhejiang Province, China - Chaojun Ouyang; Wei Zhao; Huicong An; Shu Zhou; Dongpo Wang; Qiang Xu; Weile Li; Dalei Peng (Landslides, 2019)

Dynamical process of the Hongshiyan landslide induced by the 2014 Ludian earthquake and stability evaluation of the back scarp of the remnant slope - Hai-Bo Li; Xiao-Wen Li; Yu Ning; Shu-Fang Jiang; Jia-Wen Zhou (Bulletin of Engineering Geology and the Environment, 2019)

Threshold sediment flux for the formation of river deltas in Hainan Island, southern China - Gaocong Li; Liang Zhou; Yali Qi; Shu Gao (Journal of Geographical Sciences, 2019)

An invasive population of Solidago canadensis is less sensitive to warming and nitrogen-addition than its native population in an invaded range - Yang Peng; Jian-Xia Yang; Xiao-Hui Zhou; Pei-Hao Peng; Jing-Ji Li; Shu-Min Zhang; Wei-Ming He (Biological Invasions, 2019)

A new regulator RsdA mediating fungal secondary metabolism has a detrimental impact on asexual development in Pestalotiopsis fici - Shuang Zhou; Peng Zhang; Haichuan Zhou; Xingzhong Liu; Shu‐Ming Li; Liangdong Guo; Kuan Li; Wen‐Bing Yin (Environmental Microbiology, 2019)
Summary Secondary metabolite (SM) production and development are correlated processes in fungi that are often coordinated by pleiotropic regulators. The eukaryotic regulators are critical players in mediating SM production related to fungal development, yet little data are available to support this hypothesis. In this study, a global regulator, RsdA ( r egulation of s econdary metabolism and d evelopment), was identified through genome‐wide analysis and deletion of the regulator gene in the endophytic fungus Pestalotiopsis fici . Here, we established that RsdA regulation of SMs is accompanied by the repression of asexual development. Deletion of rsdA significantly reduces not only asexual development, resulting in low sporulation and abnormal conidia, but also the major SM production, while remarkably increasing the melanin production. Overproduction of melanin leads to the formation of unusual, heavily pigmented hyphae. Transcriptome analysis data provide the evidence that RsdA globally regulates genes involved in secondary metabolism and asexual development. Double deletion of rsdA and the melanin polyketide synthase gene PfmaE confirm that RsdA regulation of asexual development is independent of the melanin biosynthetic pathway. Finally, our results demonstrate that RsdA can be used for the discovery of secondary metabolites in filamentous fungi.

Retraction Note to: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

Irinotecan Alters the Disposition of Morphine Via Inhibition of Organic Cation Transporter 1 (OCT1) and 2 (OCT2) - Peng Zhu; Zhi Ye; Dong Guo; Zongping Xiong; Shiqiong Huang; Jun Guo; Wei Zhang; James E. Polli; Honghao Zhou; Qing Li; Yan Shu (Pharmaceutical Research, 2018)

Analysis of slight precipitation in China during the past decades and its relationship with advanced very high radiometric resolution normalized difference vegetation index - Xinyue Li; Yves Balkanski; Zhengfang Wu; Thomas Gasser; Philippe Ciais; Feng Zhou; Laurent Li; Shu Tao; Shushi Peng; Shilong Piao; Rong Wang; Tao Wang; et al. (International Journal of Climatology, 2018)
Precipitation is one of the most important factors determining the occurrence of extreme hydro‐meteorological events and water resource availability. Precipitation in different grades has diverse ecological effects, and slight precipitation (SP, defined as 0.1–1.0 mm/day) is the minimal level among them. In this study, we investigated SP trends from 1961 to 2013, as well as the relationship between SP and advanced very high radiometric resolution (AVHRR) normalized difference vegetation index (NDVI) in China during growing season from 1981 to 2006. The distributions and trends of SP were analysed by calculating the daily precipitation data. The average annual slight precipitation amount (SPA) and the number of slight precipitation days (SPD), derived from 839 monitoring stations in China, show a decreasing trend over the last five decades, which is in agreement with total precipitation (TP) but in different rates. When the trend was analysed seasonally, SP in most stations decreases significantly in September–October–November (SON) and June–July–August (JJA), and the largest decrease is found in SON. About 49.5 and 68.7% of monitoring stations show a decreasing trend in SON, in both SPA and SPD, whereas the trend is less popular in March–April–May (MAM, SPA: 19.7%, SPD: 41.4%) and December–January–February (JJF, SPA: 25.6%, SPD: 43.1%). Moreover, our analysis indicates that the decrease of SP is mainly due to the decrease of SPD as the median amount of daily SP was unchanged over the past five decades (close to 0.3 mm/day). Based on 26‐year (1981–2006) semi‐monthly AVHRR NDVI data and the records of SP data, the relationship between AVHRR NDVI and SP was also investigated. In regions with lower (

Separate Neural Networks for Gains and Losses in Intertemporal Choice - Yang-Yang Zhang; Lijuan Xu; Zhu-Yuan Liang; Kun Wang; Bing Hou; Yuan Zhou; Shu Li; Tianzi Jiang (Neuroscience Bulletin, 2018)

CYP46A1 and the APOEε4 Allele Polymorphisms Correlate with the Risk of Alzheimer’s Disease - Ling Li; Fan Zeng; Yu-Hui Liu; Hui-Yun Li; Shu-Yang Dong; Ze-Yan Peng; Yan-Jiang Wang; Hua-Dong Zhou (Molecular Neurobiology, 2018)

Three new flavonoid glycosides from Smilax glabra and their anti-inflammatory activity - Jicheng Shu; Linyu Li; Meng Zhou; Jiangli Yu; Caiying Peng; Feng Shao; Ronghua Liu; Genhua Zhu; Huilian Huang (Natural Product Research, 2018)

RETRACTED ARTICLE: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

A New Advance Classification Method for Surrounding Rock in Tunnels Based on the Set-Pair Analysis and Tunnel Seismic Prediction System - Lin Bu; Shu-cai Li; Shao-shuai Shi; Xiao-kun Xie; Li-ping Li; Zong-qing Zhou; Zhi-jie Wen (Geotechnical and Geological Engineering, 2018)

Design of a Displacement Monitoring System Based on Optical Grating and Numerical Verification in Geomechanical Model Test of Water Leakage of Tunnel - Shang-qu Sun; Shu-cai Li; Li-ping Li; Shao-shuai Shi; Zong-qing Zhou; Cheng-lu Gao (Geotechnical and Geological Engineering, 2018)

Failure mechanisms and characteristics of the 2016 catastrophic rockslide at Su village, Lishui, China - Chaojun Ouyang; Wei Zhao; Qiang Xu; Dalei Peng; Weile Li; Dongpo Wang; Shu Zhou; Shunwei Hou (Landslides, 2018)

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

Diversity effect of capsaicin on different types of skeletal muscle - Gan Zhou; Lina Wang; Yaqiong Xu; Kelin Yang; Lv Luo; Leshan Wang; Yongxiang Li; Jiawen Wang; Gang Shu; Songbo Wang; Ping Gao; Xiaotong Zhu; et al. (Molecular and Cellular Biochemistry, 2018)

Efficacy of carbon dioxide treatments for the control of the two-spotted spider mite, Tetranychus urticae, and treatment impact on plant seedlings - Ya-Jun Gong; Li-Jun Cao; Ze-Hua Wang; Xiao-Yi Zhou; Jin-Cui Chen; Ary Anthony Hoffmann; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Regulation of autophagy by tea polyphenols in diabetic cardiomyopathy - Hui Zhou; Yan Chen; Shu-wei Huang; Peng-fei Hu; Li-jiang Tang (Journal of Zhejiang University-SCIENCE B, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Characterization of a novel dsRNA mycovirus isolated from strain A105 of Rhizoctonia solani AG-1 IA - Meiling Zhang; Li Zheng; Chen Liu; Canwei Shu; Erxun Zhou (Archives of Virology, 2018)

RETRACTED ARTICLE: Downregulation of the Long Non-Coding RNA Meg3 Promotes Angiogenesis After Ischemic Brain Injury by Activating Notch Signaling - Juan Liu; Qing Li; Kun-shan Zhang; Bin Hu; Xin Niu; Shu-min Zhou; Si-guang Li; Yu-ping Luo; Yang Wang; Zhi-feng Deng (Molecular Neurobiology, 2017)
Angiogenesis after ischemic brain injury contributes to the restoration of blood supply in the ischemic zone. Strategies to improve angiogenesis may facilitate the function recovery after stroke. Recent researches have demonstrated that dysfunction of long non-coding RNAs are associated with angiogenesis. We have previously reported that long non-coding RNAs (lncRNAs) are aberrantly expressed in ischemic stroke. However, little is known about long non-coding RNAs and theirs role in angiogenesis after stroke. In this study, we identified a rat lncRNAs, Meg3, and found that Meg3 was significantly decreased after ischemic stroke. Overexpression of Meg3 suppressed functional recovery and decreased capillary density after ischemic stroke. Downregulation of Meg3 ameliorated brain lesion and increased angiogenesis after ischemic stroke. Silencing of Meg3 resulted in a proangiogenic effect evidenced by increased endothelial cell migration, proliferation, sprouting, and tube formation. Mechanistically, we showed that Meg3 negatively regulated notch pathway both in vivo and in vitro. Inhibition of notch signaling in endothelial cells reversed the proangiogenic effect induced by Meg3 downregulation. This study revealed the function of Meg3 in ischemic stroke and elucidated its mechanism in angiogenesis after ischemic stroke.

Characterization of the melanocortin-4 receptor gene from Spinibarbus hollandi and the association between its polymorphisms and S. hollandi growth traits - Yang Yang; Qiang Li; Hu Shu; Huiqiang Zhou; Xin Li; Liping Hou (Fisheries Science, 2017)

Global forest carbon uptake due to nitrogen and phosphorus deposition from 1850 to 2100 - Rong Wang; Daniel Goll; Yves Balkanski; Didier Hauglustaine; Olivier Boucher; Philippe Ciais; Ivan Janssens; Josep Penuelas; Bertrand Guenet; Jordi Sardans; Laurent Bopp; Nicolas Vuichard; et al. (Global Change Biology, 2017)
Spatial patterns and temporal trends of nitrogen (N) and phosphorus (P) deposition are important for quantifying their impact on forest carbon (C) uptake. In a first step, we modeled historical and future change in the global distributions of the atmospheric deposition of N and P from the dry and wet deposition of aerosols and gases containing N and P. Future projections were compared between two scenarios with contrasting aerosol emissions. Modeled fields of N and P deposition and P concentration were evaluated using globally distributed in situ measurements. N deposition peaked around 1990 in European forests and around 2010 in East Asian forests, and both increased sevenfold relative to 1850. P deposition peaked around 2010 in South Asian forests and increased 3.5‐fold relative to 1850. In a second step, we estimated the change in C storage in forests due to the fertilization by deposited N and P (∆C ν dep ), based on the retention of deposited nutrients, their allocation within plants, and C:N and C:P stoichiometry. ∆C ν dep for 1997–2013 was estimated to be 0.27 ± 0.13 Pg C year −1 from N and 0.054 ± 0.10 Pg C year −1 from P, contributing 9% and 2% of the terrestrial C sink, respectively. Sensitivity tests show that uncertainty of ∆C ν dep was larger from P than from N, mainly due to uncertainty in the fraction of deposited P that is fixed by soil. ∆ C P dep was exceeded by ∆ C N dep over 1960–2007 in a large area of East Asian and West European forests due to a faster growth in N deposition than P. Our results suggest a significant contribution of anthropogenic P deposition to C storage, and additional sources of N are needed to support C storage by P in some Asian tropical forests where the deposition rate increased even faster for P than for N.

Different effects of neuropeptide Y on proliferation of vascular smooth muscle cells via regulation of Geminin - Zhou-qin Jiang; You-li Zhou; Xia Chen; Lin-yu Li; Shi-yu Liang; Shu Lin; Mao-qin Shu (Molecular and Cellular Biochemistry, 2017)

Deep Fracturing of the Hard Rock Surrounding a Large Underground Cavern Subjected to High Geostress: In Situ Observation and Mechanism Analysis - Xia-Ting Feng; Shu-Feng Pei; Quan Jiang; Yang-Yi Zhou; Shao-Jun Li; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Morphological plasticity in response to population density varies with soil conditions and growth stage in Abutilon theophrasti (Malvaceae) - Shu Wang; Lei Li; Dao-Wei Zhou (Plant Ecology, 2017)

Nearly a decade‐long repeatable seasonal diversity patterns of bacterioplankton communities in the eutrophic Lake Donghu (Wuhan, China) - Qingyun Yan; James C. Stegen; Yuhe Yu; Ye Deng; Xinghao Li; Shu Wu; Lili Dai; Xiang Zhang; Jinjin Li; Chun Wang; Jiajia Ni; Xuemei Li; et al. (Molecular Ecology, 2017)
Uncovering which environmental factors govern community diversity patterns and how ecological processes drive community turnover are key questions related to understand the community assembly. However, the ecological mechanisms regulating long‐term variations of bacterioplankton communities in lake ecosystems remain poorly understood. Here we present nearly a decade‐long study of bacterioplankton communities from the eutrophic Lake Donghu (Wuhan, China) using 16S rRNA gene amplicon sequencing with MiSeq platform. We found strong repeatable seasonal diversity patterns in terms of both common (detected in more than 50% samples) and dominant (relative abundance >1%) bacterial taxa turnover. Moreover, community composition tracked the seasonal temperature gradient, indicating that temperature is a key environmental factor controlling observed diversity patterns. Total phosphorus also contributed significantly to the seasonal shifts in bacterioplankton composition. However, any spatial pattern of bacterioplankton communities across the main lake areas within season was overwhelmed by their temporal variabilities. Phylogenetic analysis further indicated that 75%–82% of community turnover was governed by homogeneous selection due to consistent environmental conditions within seasons, suggesting that the microbial communities in Lake Donghu are mainly controlled by niche‐based processes. Therefore, dominant niches available within seasons might be occupied by similar combinations of bacterial taxa with modest dispersal rates throughout different lake areas.

First complete genome sequence of parainfluenza virus 5 isolated from lesser panda - Jun-Qiong Zhai; Shao-Lun Zhai; Tao Lin; Jian-Kui Liu; He-Xing Wang; Bing Li; He Zhang; Shu-Zhan Zou; Xia Zhou; Meng-Fan Wu; Wu Chen; Man-Lin Luo (Archives of Virology, 2017)

Classifying the sedimentary environments of the Xincun Lagoon, Hainan Island, by system cluster and principal component analyses - Yang Yang; Shu Gao; Liang Zhou; Yunwei Wang; Gaocong Li; Yaping Wang; Zhuochen Han; Peihong Jia (Acta Oceanologica Sinica, 2017)

Typhoon events recorded in coastal lagoon deposits, southeastern Hainan Island - Liang Zhou; Shu Gao; Yang Yang; Yangyang Zhao; Zhuochen Han; Gaocong Li; Peihong Jia; Yong Yin (Acta Oceanologica Sinica, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Developing a rat model of dilated cardiomyopathy with improved survival - Li-juan Shen; Shu Lu; Yong-hua Zhou; Lan Li; Qing-min Xing; Yong-liang Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

Yield–density relationships of above- and belowground organs in Allium cepa var. aggregatum populations - Lei Li; Jacob Weiner; Ying Wang; Shu Wang; Dao-Wei Zhou (Plant Ecology, 2016)

Human amniotic epithelial stem cells promote wound healing by facilitating migration and proliferation of keratinocytes via ERK, JNK and AKT signaling pathways - Bin Zhao; Jia-Qi Liu; Zhao Zheng; Jun Zhang; Shu-Yue Wang; Shi-Chao Han; Qin Zhou; Hao Guan; Chao Li; Lin-Lin Su; Da-Hai Hu (Cell and Tissue Research, 2016)

QTL mapping of dehiscence length at the basal part of thecae related to heat tolerance of rice (Oryza sativa L.) - Ling Zhao; Chun-Fang Zhao; Li-Hui Zhou; Jing Lin; Qing-Yong Zhao; Zhen Zhu; Tao Chen; Shu Yao; Toshihiro Hasegawa; Tsutomu Matsui; Cai-Lin Wang (Euphytica, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Study on Longitudinal Deformation Profile of Rock Mass in a Subsea Tunnel - Shu-Guang Song; Shu-Cai Li; Li-Ping Li; Qian-Qing Zhang; Kai Wang; Yi Zhou; Hong-Liang Liu (Marine Georesources & Geotechnology, 2016)

Air quality improvement during 2010 Asian games on blood coagulability in COPD patients - Zili Zhang; Jian Wang; Meihua Guo; Mingmei Xiong; Qipeng Zhou; Defu Li; Jiaze Shu; Wenju Lu; Dejun Sun (Environmental Science and Pollution Research, 2016)

On the variability of near-bed floc size due to complex interactions between turbulence, SSC, settling velocity, effective density and the fractal dimension of flocs - Yang Yang; Ya Ping Wang; Chunyan Li; Shu Gao; Benwei Shi; Liang Zhou; Dandan Wang; Gaocong Li; Chen Dai (Geo-Marine Letters, 2016)

Sediment resuspension in tidally dominated coastal environments: new insights into the threshold for initial movement - Yang Yang; Ya Ping Wang; Shu Gao; Xiao Hua Wang; Ben Wei Shi; Liang Zhou; Dan Dan Wang; Chen Dai; Gao Cong Li (Ocean Dynamics, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Risk analysis and emergency actions for Hongshiyan barrier lake - Xingbo Zhou; Zuyu Chen; Shu Yu; Lin Wang; Gang Deng; Peijun Sha; Shouyi Li (Natural Hazards, 2015)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

The prevalence and determinants of drug-resistance-associated mutations in the HIV-1-infected MSM population of Henan Province in China - Li-Juan Hou; Hong-Wei Wang; Shu-Peng Duan; Ya Zhuo; Yan-Cai Zhou; Hong-Jie Wu; Bao-Sheng Shen (Archives of Virology, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Association analysis revealed one susceptibility locus for vitiligo with immune-related diseases in the Chinese Han population - Shu Li; Weiyi Yao; Qian Pan; Xianfa Tang; Suli Zhao; Wenjun Wang; Zhengwei Zhu; Jinping Gao; Yujun Sheng; Fusheng Zhou; Xiaodong Zheng; Xianbo Zuo; et al. (Immunogenetics, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

ACE2 and Ang-(1–7) protect endothelial cell function and prevent early atherosclerosis by inhibiting inflammatory response - Yue-Hui Zhang; Yong-huan Zhang; Xue-Fei Dong; Qing-Qing Hao; Xiao-Ming Zhou; Qing-Tao Yu; Shu-Ying Li; Xu Chen; Abdulai Fallah Tengbeh; Bo Dong; Yun Zhang (Inflammation Research, 2015)

Evaluation of the effect of stock enhancement in the coastal waters of G uangdong, C hina - P. Chen; C. Qin; J. Yu; L. Shu; X. Li; Y. Zhou; H. Yuan (Fisheries Management and Ecology, 2015)
A total of 14.573 million fish fry and 96.32 million shrimp larvae were released across 31 locations into the coastal waters off G uangdong, C hina, in 2010. The released fish and shrimp were sampled through a combination of market and fishing log‐book surveys. The combined fishery production reached 362 868 kg. The input–output ratio was 1:5.99 for released fish (over 3 years) and 1:11.01 for released shrimp (over 2 years). The average increase in income was 721 RMB per capita. Approximately 240 thousand fish (after 3 years) and 1.2 million shrimp (after 2 years) survived to sexual maturity and could contribute to the spawning stock. The stockings were approximately one‐seventh of the fish and one‐half of the shrimp stocking carrying capacities, respectively. Based on these results, the intensity of stocking could be increased. Stocking and recapture strategies should be adjusted to align with the optimal stocking carrying capacity determined from this study.

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Novel Rare Earth Tungstoarsenate Heteropolyoxometalates K11[Ln(AsW11O39)2]·xH2O (Ln = La, Nd, Sm) Binding to Bovine Serum Albumin: Spectroscopic Approach - Shan Jiang; Li-Yang Cheng; Ai-Min Bai; Shu Zhou; Yan-Jun Hu (Biological Trace Element Research, 2015)

Hymenobacter latericoloratus sp. nov. and Hymenobacter luteus sp. nov., isolated from freshwater sediment - Lan Liu; En-Min Zhou; Jian-Yu Jiao; Deene Manikprabhu; Hong Ming; Wei-Hong Liu; Wael N. Hozzein; Wen-Sheng Shu; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Gene expression pattern of insect fat body cells from in vitro challenge to cell line establishment - Huan Zhang; Qian Meng; Ping Tang; Xuan Li; Wei Zhu; Guiling Zhou; Ruihao Shu; Jihong Zhang; Qilian Qin (In Vitro Cellular & Developmental Biology - Animal, 2014)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

Two new truffles species, Tuber alboumbilicum and Tuber pseudobrumale from China - Shu-Hong Li; Lin-Yong Zheng; Cheng-Yi Liu; Yun Wang; Lin Li; Yong-Chang Zhao; Xiao-Lei Zhang; Mei Yang; Hai-Kuan Xiong; Yuan Qing; Li Wang; De-Qun Zhou (Mycological Progress, 2014)

Probing the Neural Basis of Superstition - Li-Lin Rao; Yu Zheng; Yuan Zhou; Shu Li (Brain Topography, 2014)

Modeling of Friedreich ataxia-related iron overloading cardiomyopathy using patient-specific-induced pluripotent stem cells - Yee-Ki Lee; Philip Wing-Lok Ho; Revital Schick; Yee-Man Lau; Wing-Hon Lai; Ting Zhou; Yanhua Li; Kwong-Man Ng; Shu-Leung HO; Miguel Angel Esteban; Ofer Binah; Hung-Fat Tse; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Influence of ciprofloxacin on microbial community structure and function in soils - Hao Cui; Shu-Ping Wang; Jin Fu; Zhi-Qiang Zhou; Na Zhang; Li Guo (Biology and Fertility of Soils, 2014)

The effects of dietary thiamin on oxidative damage and antioxidant defence of juvenile fish - Xue-Yin Li; Hui-Hua Huang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Shu-Hong Li; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Effect of dietary lysine on growth, intestinal enzymes activities and antioxidant status of sub-adult grass carp (Ctenopharyngodon idella) - Xue-Yin Li; Ling Tang; Kai Hu; Yang Liu; Wei-Dan Jiang; Jun Jiang; Pei Wu; Gang-Fu Chen; Shu-Hong Li; Sheng-Yao Kuang; Lin Feng; Xiao-Qiu Zhou (Fish Physiology and Biochemistry, 2014)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Antioxidant status of serum, muscle, intestine and hepatopancreas for fish fed graded levels of biotin - Lin Feng; Shu Zhao; Gangfu Chen; Weidan Jiang; Yang Liu; Jun Jiang; Kai Hu; Shuhong Li; Xiaoqiu Zhou (Fish Physiology and Biochemistry, 2014)

Efficacy of Various Combined Blood Purification Techniques for Treating Patients with Non-viral Acute Liver Failure - Mao-qin Li; Jia-qiong Li; Zai-xiang Shi; Ji-yuan Xu; Zhou Zhang; Fei Lu; Lin Li; Yan-jun Xu; Xun Mo; Bo Lu; Xiao-meng Wang; Li-li Ma; et al. (Cell Biochemistry and Biophysics, 2014)

Alterations of the interstitial cells of Cajal and the microstructure of the gastrointestinal tract in KIT distal kinase mutant mice - Xiaoshuang Li; Hong Xue; Qian Kang; Haimei Sun; Shu Yang; Guoquan Zhang; Deshan Zhou (Cell and Tissue Research, 2014)

Overexpression of CsCLCc, a Chloride Channel Gene from Poncirus trifoliata, Enhances Salt Tolerance in Arabidopsis - Qingjiang Wei; Yongzhong Liu; Gaofeng Zhou; Qiaohong Li; Chengquan Yang; Shu-ang Peng (Plant Molecular Biology Reporter, 2013)

Exploring the pattern of phenotypic and genetic polymorphism in the arsenic hyperaccumulator Pteris vittata L. (Chinese brake fern) - Bing Yang; Alessio Mengoni; Ye-Ling Huang; Xiong-Lei He; Jin-Tian Li; Bin Liao; Mi Zhou; Wen-Sheng Shu (Plant and Soil, 2013)

E2F1-mediated DNA damage is implicated in 8-Cl-adenosine-induced chromosome missegregation and apoptosis in human lung cancer H1299 cells - Yu-Ying Han; Zhe Zhou; Ji-Xiang Cao; Ya-Qiong Jin; Shu-Yan Li; Ju-Hua Ni; Guo-Shun An; Yu-Xiang Zhang; Hong-Ti Jia (Molecular and Cellular Biochemistry, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Hierarchically Clustering to 1,033 Genes Differentially Expressed in Mouse Superior Colliculus in the Courses of Optic Nerve Development and Injury - Qiang Mei; Yan-qi Zhang; Jian-jun Liu; Cheng-ren Li; Xing-shu Chen; Hong-li Li; Mao-lin Qin; Ya-zhou wu; Yun-lai Liu; Wen-qin Cai (Cell Biochemistry and Biophysics, 2013)

Molecular characterization and tissue localization of sensory neuron membrane protein from Chinese honey bee, Apis cerana cerana (Hymenoptera: Apidae) - Ying-Ying Hu; Shu-Fa Xu; Abebe Jenberie Wubie; Wei Li; Jia-Xing Huang; Zhan-Bao Guo; Ting Zhou (Applied Entomology and Zoology, 2013)

β-Glucanase specific expression in the parotid gland of transgenic mice - Li-zheng Guan; Yu-ping Sun; Qian-yun Xi; Jing-lan Wang; Jun-yun Zhou; Gang Shu; Qing-yan Jiang; Yong-liang Zhang (Transgenic Research, 2013)

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Bacterial and archaeal diversities in Y unnan and T ibetan hot springs, C hina - Zhao‐Qi Song; Feng‐Ping Wang; Xiao‐Yang Zhi; Jin‐Quan Chen; En‐Min Zhou; Feng Liang; Xiang Xiao; Shu‐Kun Tang; Hong‐Chen Jiang; Chuanlun L. Zhang; Hailiang Dong; Wen‐Jun Li (Environmental Microbiology, 2013)
Summary Thousands of hot springs are located in the north‐eastern part of the Y unnan– T ibet geothermal zone, which is one of the most active geothermal areas in the world. However, a comprehensive and detailed understanding of microbial diversity in these hot springs is still lacking. In this study, bacterial and archaeal diversities were investigated in 16 hot springs ( pH 3.2–8.6; temperature 47–96° C ) in Y unnan P rovince and T ibet, C hina by using a barcoded 16 S rRNA gene‐pyrosequencing approach. A quificae , P roteobacteria , F irmicutes , D einococcus‐ T hermus and B acteroidetes comprised the large portion of the bacterial communities in acidic hot springs. Non‐acidic hot springs harboured more and variable bacterial phyla than acidic springs. D esulfurococcales and unclassified C renarchaeota were the dominated groups in archaeal populations from most of the non‐acidic hot springs; whereas, the archaeal community structure in acidic hot springs was simpler and characterized by S ulfolobales and T hermoplasmata . The phylogenetic analyses showed that A quificae and C renarchaeota were predominant in the investigated springs and possessed many phylogenetic lineages that have never been detected in other hot springs in the world. Thus findings from this study significantly improve our understanding of microbial diversity in terrestrial hot springs.

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Ventral medial prefrontal functional connectivity and emotion regulation in chronic schizophrenia: A pilot study - Feng-Mei Fan; Shu-Ping Tan; Fu-De Yang; Yun-Long Tan; Yan-Li Zhao; Nan Chen; Bin-Bin Li; Chong-Sheng Song; Yun-Hui Wang; Zhen Jin; Dong-Feng Zhou; Michael P. Milham; et al. (Neuroscience Bulletin, 2013)

The Role of Neuroglobin in the Neuroprotection of Limb Ischemic Preconditioning in Rats - Shu-Qin Li; Wen-Bin Li; Min Zhang; Yu-Zhou Wu; Yu-Yan Hu (Molecular Neurobiology, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

Methylglyoxal Induces Tau Hyperphosphorylation via Promoting AGEs Formation - Xiao-Hong Li; Jia-Zhao Xie; Xia Jiang; Bing-Ling Lv; Xiang-Shu Cheng; Lai-Ling Du; Jia-Yu Zhang; Jian-Zhi Wang; Xin-Wen Zhou (NeuroMolecular Medicine, 2012)

Protective effect of rat pancreatic progenitors cells expressing Pdx1 and nestin on islets survival and function in vitro and in vivo - Shu-yan Zhou; Yu-sen Zhang; Qing Li; Yi Zhang; Hui Qi; Han-xin Zhou; Chun-yan Deng; Fu-rong Li (Journal of Physiology and Biochemistry, 2012)

Lihuaxuella thermophila gen. nov., sp. nov., isolated from a geothermal soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Bing-Huo Zhang; Ji-Cheng Yao; Shu-Kun Tang; En-Min Zhou; Yi-Rui Yin; Da-Qiao Wei; Hong Ming; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Efficacy of a Therapeutic Vaccine Using Mutated β-amyloid Sensitized Dendritic Cells in Alzheimer’s Mice - Zhongqiu Luo; Jialin Li; Neel R. Nabar; Xiaoyang Lin; Ge Bai; Jianfeng Cai; Shu-Feng Zhou; Chuanhai Cao; Jinhuan Wang (Journal of Neuroimmune Pharmacology, 2012)

The expression of pentraxin 3 and tumor necrosis factor-alpha is increased in preeclamptic placental tissue and maternal serum - Ping Zhou; Xin Luo; Hong-bo Qi; Wen-jun Zong; Hua Zhang; Dan-dan Liu; Qing-shu Li (Inflammation Research, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Paenibacillus frigoriresistens sp. nov., a novel psychrotroph isolated from a peat bog in Heilongjiang, Northern China - Hong Ming; Guo-Xing Nie; Hong-Chen Jiang; Tian-Tian Yu; En-Min Zhou; Hui-Gen Feng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Kineococcus glutineturens sp. nov., isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Jing Zhang; Hui-Gen Feng; Shuai Li; Tian-Tian Yu; En-Min Zhou; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Thermoactinospora rubra gen. nov., sp. nov., a thermophilic actinomycete isolated from Tengchong, Yunnan province, south–west China - En-Min Zhou; Shu-Kun Tang; Carsten Sjøholm; Zhao-Qi Song; Tian-Tian Yu; Ling-Ling Yang; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Clinical characteristics of hepatitis B virus infection in middle school students born after the universal infant vaccination program in Shanghai, China - Wei-Ling Wang; Zhi-Jun Shu; Li-Xia Zhou; Yan-Rong Zhao (Archives of Virology, 2012)

Geodermatophilus nigrescens sp. nov., isolated from a dry-hot valley - Guo-Xing Nie; Hong Ming; Shuai Li; En-Min Zhou; Juan Cheng; Tian-Tian Yu; Jing Zhang; Hui-Gen Feng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Pseudonocardia yuanmoensis sp. nov., a novel actinobacterium isolated from soil in Yunnan, south-west China - Guo-Xing Nie; Hong Ming; Da-Qiao Wei; En-Min Zhou; Xia Tang; Juan Cheng; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Begomovirus–whitefly mutualism is achieved through repression of plant defences by a virus pathogenicity factor - TONG ZHANG; JUN‐BO LUAN; JIN‐FENG QI; CHANG‐JUN HUANG; MENG LI; XUE‐PING ZHOU; SHU‐SHENG LIU (Molecular Ecology, 2012)
Plant‐mediated interactions between herbivorous arthropods and pathogens transmitted by herbivores are important determinants of the population dynamics of both types of organisms in the field. The role of plant defence in mediating these types of tripartite interactions have been recognized but rarely examined especially at the physiological and molecular levels. Our previous work shows that a worldwide invasive whitefly can establish mutualism with the begomovirus Tomato yellow leaf curl China virus (TYLCCNV) via crop plants. Here, we show that TYLCCNV and betasatellite co‐infection suppresses jasmonic acid defences in the plant. Impairing or enhancing defences mediated by jasmonic acid in the plant enhances or depresses the performance of the whitefly. We further demonstrate that the pathogenicity factor βC1 encoded in the betasatellite is responsible for the initiation of suppression on plant defences and contributes to the realization of the virus–vector mutualism. By integrating ecological, mechanistic and molecular approaches, our study reveals a major mechanism of the plant‐mediated mutualism between a virus and its vector. As the test plant is an important economic crop, the results also have substantial implications for developing novel strategies for management of crop viruses and the insect vectors associated with them.

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Expression and roles of Slit/Robo in human ovarian cancer - Cai Feng Dai; Yi Zhou Jiang; Yan Li; Kai Wang; Pei Shu Liu; Manish S. Patankar; Jing Zheng (Histochemistry and Cell Biology, 2011)

Agrobacterium tumefaciens-mediated Transformation of A Taxol-Producing Endophytic Fungus, Cladosporium cladosporioides MD2 - Peng Zhang; Ting-Ting Liu; Peng-Peng Zhou; Shu-Tao Li; Long-Jiang Yu (Current Microbiology, 2011)

Mutations of the GATA4 and NKX2.5 genes in Chinese pediatric patients with non-familial congenital heart disease - Ting Peng; Li Wang; Shu-Feng Zhou; Xiaotian Li (Genetica, 2010)

Diversity of Crenarchaeota in terrestrial hot springs in Tengchong, China - Zhao-Qi Song; Jing-Quan Chen; Hong-Chen Jiang; En-Min Zhou; Shu-Kun Tang; Xiao-Yang Zhi; Li-Xin Zhang; Chuan-Lun L. Zhang; Wen-Jun Li (Extremophiles, 2010)

Prediction of summer grain crop yield with a process-based ecosystem model and remote sensing data for the northern area of the Jiangsu Province, China - Weimin Ju; Ping Gao; Yanlian Zhou; Jing M. Chen; Shu Chen; Xianfeng Li (International Journal of Remote Sensing, 2010)

Viral infection of tobacco plants improves performance of Bemisia tabaci but more so for an invasive than for an indigenous biotype of the whitefly - Jian Liu; Meng Li; Jun-min Li; Chang-jun Huang; Xue-ping Zhou; Fang-cheng Xu; Shu-sheng Liu (Journal of Zhejiang University-SCIENCE B, 2010)

Probabilistic Ecological Risk Assessment and Source Apportionment of Polycyclic Aromatic Hydrocarbons in Surface Sediments from Yellow Sea - Ai-Xia Liu; Yin-Hai Lang; Li-Dong Xue; Shu-Lin Liao; Hong Zhou (Bulletin of Environmental Contamination and Toxicology, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Insights into the Substrate Specificity, Inhibitors, Regulation, and Polymorphisms and the Clinical Impact of Human Cytochrome P450 1A2 - Shu-Feng Zhou; Li-Ping Yang; Zhi-Wei Zhou; Ya-He Liu; Eli Chan (The AAPS Journal, 2009)

Sequence Polymorphism and Evolution of Three Cetacean MHC Genes - Shi Xia Xu; Wen Hua Ren; Shu Zhen Li; Fu Wen Wei; Kai Ya Zhou; Guang Yang (Journal of Molecular Evolution, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Identification of QTLs for the resistance to rice stripe virus in the indica rice variety Dular - Shu-Jun Wu; Huan Zhong; Yong Zhou; Hui Zuo; Li-Hui Zhou; Jin-Yan Zhu; Cao-Qiu Ji; Shi-Liang Gu; Ming-Hong Gu; Guo-Hua Liang (Euphytica, 2009)

Relationships Among Genetic Makeup, Active Ingredient Content, and Place of Origin of the Medicinal Plant Gastrodia Tuber - Jun Tao; Zhi-yong Luo; Chikira Ismail Msangi; Xiao-shun Shu; Li Wen; Shui-ping Liu; Chang-quan Zhou; Rui-xin Liu; Wei-xin Hu (Biochemical Genetics, 2009)

Culturable and molecular phylogenetic diversity of microorganisms in an open-dumped, extremely acidic Pb/Zn mine tailings - Gui-Liang Tan; Wen-Sheng Shu; Kevin B. Hallberg; Fang Li; Chong-Yu Lan; Wen-Hua Zhou; Li-Nan Huang (Extremophiles, 2008)

Association Between Alzheimer’s Disease and the NOS3 gene Glu298Asp Polymorphism in Chinese - Binbin Wang; Sainan Tan; Ze Yang; Yan-Chen Xie; Jing Wang; Sirui Zhou; Shu Li; Chenguang Zheng; Xu Ma (Journal of Molecular Neuroscience, 2008)

Forms and balance of nitrogen and phosphorus in cage culture waters in Guangdong Province, China - Yanmao Wen; Xiange Wei; Tingfei Shu; Jingfeng Zhou; Guanghui Yu; Feng Li; Yanyun Huang (Chinese Geographical Science, 2007)

A follow-up study of mortality among the arseniasis patients exposed to indoor combustion of high arsenic coal in Southwest Guizhou Autonomous Prefecture, China - Ji-gang Chen; Yu-gang Chen; Yun-shu Zhou; Guo-fang Lin; Xiu-jie Li; Chao-gang Jia; Wei-chao Guo; Hui Du; Hong-chao Lu; Hong Meng; Xin-jiang Zhang; Klaus Golka; et al. (International Archives of Occupational and Environmental Health, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

Intra- and Inter-ethnic Differences in the Allele Frequencies of Cytochrome P450 2B6 Gene in Chinese - Su Guan; Min Huang; Xin Li; Xiao Chen; Eli Chan; Shu-Feng Zhou (Pharmaceutical Research, 2006)

Dissociation (Ds) constructs, mapped Ds launch pads and a transiently-expressed transposase system suitable for localized insertional mutagenesis in rice - Narayana M. Upadhyaya; Qian-Hao Zhu; Xue-Rong Zhou; Andrew L. Eamens; Mohammad S. Hoque; Kerrie Ramm; Ramannee Shivakkumar; Kathryn F. Smith; Shu-Ting Pan; Suzhi Li; Kefan Peng; Song J. Kim; et al. (Theoretical and Applied Genetics, 2006)